Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Identifying the optimal harvest stage for forage and biogas production from sweet sorghum under semi-arid Mediterranean conditions - Recep Irfan Nazli; Burak Beyaz; Asiye Sena Cavdar; Hasan Beytullah Donmez; Muhammad Azhar Nadeem (Biomass and Bioenergy, 2027)

Risk-based adaptation framework for levees under evolving climatic and non-climatic stressors - Mohammed Azhar; Paul Kirshen; Amir AghaKouchak; Farshid Vahedifard (Water Security, 2026)

Comparative analysis of contemporary remote sensing techniques and species distribution modelling in predicting spatial distribution of coastal habitats - Louise Forsblom; Ari-Pekka Jokinen; Dimitry Van der Zande; Mihailo Azhar; Dimitar Berov; Jacob Carstensen; Vivi Drakopoulou; Vasilis Gerakaris; Hege Gundersen; Jonne Kotta; Valeria Mobilia; Nadia Papadopoulou; et al. (Remote Sensing of Environment, 2026)

Use of wild edible plants: A comparative analysis of seven plant species for potential food applications - Ehsan Ali; Muhammad Farooq Azhar (Food and Humanity, 2026)

Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

Precision Immunoregulation in transplantation: The rise of engineered Treg therapies - Mohammad Asim Azhar; Tanveer Ahmad Mir; Mohammad Afzal Khan; Alaa Alzhrani; Jahan Salma; Shadab Kazmi; Abdullah M. Assiri; Dieter C. Broering; Ahmed Yaqinuddin (Molecular Biology Reports, 2026)

Draft nuclear and complete mitochondrial genome assemblies of the flare-horned markhor (Capra falconeri): genomic resources for conservation and phylogenetics - Javeria Wali; Muhammad Waqas; Azhar Hussain Shah; Inam Ullah; Asif Mir; Zunnan Huang; Amjad Ali (Mammalian Genome, 2026)

Staphylococcus aureus biofilms: molecular mechanisms, resistance determinants, and emerging therapeutic strategies - Mohd Saleem; Azharuddin Sajid Syed Khaja; Irfan Ahmad; Yasser Alraey; Mohammad Asim Azhar; Mohd Shahid Khan (Molecular Biology Reports, 2026)

Effect of heating on the rheological and fluorescence characteristics of the wheat grit-water systems - Zhyldyzai Ozbekova; Rakhat Anarbai kyzy; Azhar Makambai kyzy; Asylbek Kulmyrzaev; Abdybek Asanaliev (Food Hydrocolloids, 2026)

Toxicological safety and stress-reducing effects of Datura metel extract in juvenile Macrobrachium rosenbergii - Azhar Ismail; Kamariah Bakar; Tan Hock Seng; Liew Hon Jung; Mohd Amran Aaqillah-Amr; Nurul Ulfah Karim (Aquaculture, 2026)

Holocene tectonic activity and slip distribution along the Himalayan Frontal Thrust in Kumaun, central Himalaya - Mitthu Dhali; Javed N. Malik; Mohd Azhar Ansari; Mahendrasinh Gadhavi; Nicolò Parrino; Pierfrancesco Burrato (Geomorphology, 2026)

Closing the selection gap in passive retrofit optimization: a pathway-based framework for resident-informed selection in old residential buildings in cold-region China - Pengfei Gao; Muhammad Farihan Irfan Mohd. Nor; Mohd Khairul Azhar Mat Sulaiman (Energy and Buildings, 2026)

A directional ejection-injection mechanism for accelerated metal coordination on an alumina-doped mesoporous silica surface - Yugo Hirade; Hiroki Iwai; Yuta Funakoshi; Yuzuru Tanabe; Masako Momotake; Azhar Alowasheeir; Pavuluri Srinivasu; Yusuke Yamauchi; Yuta Tsuji; Miharu Eguchi (Chemical Engineering Journal, 2026)

From biosynthesis to food market translation of pullulan: AI-assisted production, structure-property-function interplay, regulatory perspectives, and commercialization - Muhammad Wajid Ullah; Su Sun; Zainab Jamil; Omar Mohammad Atta; Lili Zhang; Maleeha Azhar; Hidayat Ullah; Faryal Taimour; Mazhar Ul-Islam; Sehrish Manan; Yimin Fan; Zhiguo Wang (Carbohydrate Polymers, 2026)

Environment influence on antifouling coating efficiency: evidence from the Arabian Gulf and the Sea of Oman - Azhar Al-Busaidi; Maryam Al-Memari; John A. Burt; Sergey Dobretsov (Biofouling, 2026)

Integrated SARA–Fluorescence Analysis of Crude Oil with Fraction-Specific Calibration - Azhar Kamel; Sagida Abass Hussain; Nasser M. Hadi; Jalal N. Jeber (Journal of Fluorescence, 2026)

Spatiotemporal assessment of water quality around Western Australian central business district using satellite multispectral imaging - Muhammad Hassnain; Cameron Veal; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2026)

Mode of inheritance of spinosad resistance in the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae) - Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

High-resolution species distribution modelling to guide eelgrass (Zostera marina) management - Sanjina Upadhyay Stæhr; Cordula Göke; Andreas Michael Holbach; Peter Anton Upadhyay Stæhr; Dorte Krause-Jensen; Mihailo Azhar; Jacob Carstensen (Estuarine, Coastal and Shelf Science, 2026)

Micronutrient biofortification in rice for combating hidden hunger and improving nutritional security - Amina Minahil; Adeel Khan; Azhar Mehmood; Zia-ul-qamar (Cereal Research Communications, 2026)

Improving tooth enamel remineralization with laser-assisted colloidal platinum nanoparticles: a new alternative to fluoride-based treatments - Fattin A. Fadhil; Azhar M. Haleem; Ahlam Taha Mohammed; Abdulrahman Khalaf Ali (Toxicology and Environmental Health Sciences, 2026)

Integration of IoT technology, water hyacinth phytoremediation, and activated carbon for heavy metal contaminated water treatment - B. Azhar; H. Heryanto; A. R. Arif (International Journal of Environmental Science and Technology, 2026)

A comparative assessment of energy efficiency on real structure using sensor-aided and living lab concepts - Faiza Saeed; Farrukh Arif; Nida Azhar (Innovative Infrastructure Solutions, 2026)

Genetic neglect and health inequity: the overlooked burden of Alport syndrome in Pakistan - Hamna Yaseen; Ariba Azhar Hussain Shah; Marium Nadeem; Hamza Shakeel (Journal of Community Genetics, 2026)

Blood Radon Activity and Model-Derived Uranium Estimates in Gastrointestinal Cancer Patients from Southern Iraq - Azhar S. Alaboodi; Shaymaa Awad Kadhim; Kamran Heydaryan (Biological Trace Element Research, 2026)

Age-stage, two-sex life table analysis reveals transgenerational lethal and sublethal impacts of Beauveria bassiana on Spodoptera frugiperda - Tiyyabah Khan; Hafiz Azhar Ali Khan (Crop Protection, 2026)

A Novel hybrid kinetic–equilibrium model for predicting syngas composition in coal char gasification: Coupling thin reaction zone kinetic with Gibbs free energy minimization - Takdir Syarif; Thahirah Arief; Muhammad Ikhsan Taipabu; Karthickeyan Viswananthan; Wei Wu; Badril Azhar (Fuel, 2026)

Copper-tuned bandgap engineering of ZnO/CdS nanocomposites for photocatalytic water purification and hydrogen energy production - Sibgha Shaheen; Abu Bakar Siddique; Farhat Nosheen; Azhar Abbas; Abdul Majid; Umar Nishan; Ibrahim A. Shaaban (Fuel, 2026)

Retraction notice to “Does communicable diseases (including COVID-19) may increase global poverty risk? A cloud on the horizon” [Environ. Res. 187 (2020) 109668] - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Xuan Vinh Vo; Khalid Zaman (Environmental Research, 2026)

Sustainable water circularity using electrocoagulation system for Leptobarbus Hoevenii aquaculture wastewater treatment in rural Borneo - Nazeri Abdul Rahman; Chieng Kwong Ming; Calvin Jose Jol; Allene Albania Linus; Siti Noor Linda Taib; Arif Parabi; Badrul Hisham Mohamad Jan; Astisza Syahla Ludmilla Parabi; Anthonette James; Nurshazatul'aini Abdul Mutalip; Shaleen Nur Ain Samsul; Joshua Anyi Ngau; et al. (Environmental Research, 2026)

Microwave-induced eustress in Datura innoxia: Integrated photosynthetic, oxidative, and cellular responses to a low-dose hormetic elicitor - M. Masroor A. Khan; Tahoora Batool; Azhar Ali; Saif Ali Khan; M. Naeem; Mohammad Mukarram (Biocatalysis and Agricultural Biotechnology, 2026)

Pressmud Alleviates Cadmium Stress in Wheat by Enhancing Soil Microbial Activity, Nutrient Uptake and Limiting Cd Accumulation - Basit Haider; Muhammad Imran; Fuad Ameen; Hadeeqa Arshad; Azhar Hussain; Ruijia Liu; Asif Naeem (Water, Air, & Soil Pollution, 2026)

Feature Selection and Data Decomposition-Driven Drought Forecasting: Designing Hybrid Deep Learning Models - Ayesha Parveen; Muhammad Azhar; Muhammad Gulistan; Mumtaz Ali; Aitazaz A. Farooque (Water Resources Management, 2026)

Initial Assessment of a New Olive Mill Waste-Derived Biostimulant for Mitigating Water Stress in Pomegranate Trees - Darine Tlili; Samia Abboud; Sahar Ben Abdelwaheb; Azhar Ouni; Soumaya Dbara (Applied Fruit Science, 2026)

Year-round fruiting by Muntingia calabura helps sustain urban frugivorous birds across tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ahmad Razi Norhisham; Ruzana Sanusi; Badrul Azhar (Ornithology Research, 2026)

Tissue engineering of articular cartilage using nasal chondrocytes on alginate-chitosan-based composite scaffolds - Pooja Swami; Zachary Goldman; Brandon Alba; Henintsoa Fanjaniaina Andriamifidy; Haixiang Liang; Shabirul Haque; Sadanand Pandey; Azhar Khan; Daniel A. Grande (Cell and Tissue Banking, 2026)

Machine learning, eDNA and citizen science in monitoring and assessing biodiversity and invasive alien species at sea - Angel Borja; Mihailo Azhar; Lisandro Benedetti-Cecchi; Rein Brys; Berta Companys; Alice Estrela; José A. Fernandes-Salvador; Igor Granado; Stelios Katsanevakis; Agnese Marchini; Jaume Piera; Lauriane Ribas-Deulofeu; et al. (Frontiers in Marine Science, 2026)
This research outlines the integration of machine learning, citizen science, environmental DNA (eDNA), and other emerging technologies to enhance marine biodiversity and invasive alien species monitoring, discussed during a summer school organized by several European projects in June 2025. Furthermore, monitoring approaches are increasingly complemented by remote sensing, drones, and machine learning to expand spatial coverage and improve data processing. Machine learning supports species identification across taxa through deep learning and other methods, underpinned by robust validation protocols. Frameworks such as Essential Biodiversity Variables (EBVs) and Essential Ocean Variables (EOVs) standardize data collection and interpretation, enabling hypothesis-driven monitoring and global synthesis. Computer vision models (e.g., YOLO, Mask R-CNN) and transfer learning further facilitate species identification required by EBVs. Citizen science initiatives such as iNaturalist and MINKA combine machine learning-assisted identification with expert validation, substantially broadening biodiversity monitoring. However, spatial biases and limitations persist, particularly for cryptic and deep-sea taxa. For invasive species, technologies like autonomous vehicles and eDNA sampling enhance early detection. The CIMPAL+ framework supports ecosystem-based management by assessing cumulative impacts of non-native species. Overall, these tools enhance monitoring efficiency and inclusivity but require ethical oversight, standardized protocols, and interdisciplinary collaboration to ensure scientific integrity and policy relevance.

Predicting plasma leakage in adult patients with dengue using clinical and laboratory markers at the time of emergency department presentation - Yung Ban Cheng; Aida Bustam; Khadijah Poh; Muhaimin Noor Azhar; Mohd Hafyzuddin Md Yusuf (Infectious Diseases, 2026)

Artificial intelligence based predictive simulation and decision-support framework for full scale wastewater treatment systems - Muhammad Hassnain; Cameron Veal; Sarada M.W. Lee; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2026)

Hybrid deep learning approach for detecting and classifying space debris in low Earth orbit - Eman Mahmoud; Syed Saad Azhar Ali; Abdul Jabbar Siddiqui (Journal of Space Safety Engineering, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Long term rainfall observation using climatic indices and innovative trend methods in northern Bangladesh - Azhar Uddin; J. M. Adeeb Salman Chowdhury; Most. Asikha Aktar; Md. Safayet Hossain; Md. Abdullah Al Mamun (Theoretical and Applied Climatology, 2026)

Improving subseasonal Indian summer monsoon rainfall forecasts with U-Net calibration - Emile D. Esmaili; Andrew W. Robertson; Muhammad Azhar Ehsan; Bohar Singh; Aaron Kaplan; Avijit Dey; Susmitha Joseph (Climate Dynamics, 2026)

CRISPR-based tools in food safety and microbiology: applications for pathogen detection and control - Fatima Azhar; Bi Bi Zainab Mazhari; Mohamed N. Ibrahim; Awadh Alanazi; Fakhar Islam (Archives of Microbiology, 2026)

Therapeutic and immunomodulatory effects of phage therapy in red hybrid tilapia challenged with Klebsiella pneumoniae - Anisah Azhar; Nur Syazana Aziz; Norhidayah Mohd Taufek; Subha Bhassu; Swee Seong Tang; Norhafiza Mohd Arshad (Archives of Microbiology, 2026)

Lignin Nanoparticles as a Sustainable Approach to Enhance Salt Tolerance in Pomegranate - Sahar Ben Abdelwaheb; Azhar Ouni; Josefina Bota; Samia Abboud; Jaume Puigserver; Darine Tlili; Mourad Jellali; Noomene Sleimi; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Fluid flow characterisation of naturally fractured coals in Jharia basin using cleat aperture scaling for enhanced CBM and CO2 storage potential - Fawaz Azhar; Jyotirmoy Mallik (Journal of Earth System Science, 2026)

Prevalence of Vitamin D Deficiency in Ataxia-Telangiectasia: A Systematic Review and Single Arm Meta-Analysis - Muhammad Junaid Iqbal; Muteeba Azhar; Hammad Javaid; Amina Hassan; Ayesha Masood; Michele Menotta (The Cerebellum, 2026)

Toward a climate-resilient desert, coastal city: High-resolution LCZ–WRF modeling of transformative urban greening scenarios - Christos Fountoukis; Omer Abedrabboh; Rajeswari Jayarajan Roshini; Azhar Siddique; Shamjad Moosakutty; M. Rami Alfarra (Urban Climate, 2026)

Mitigation of operational safety risks in a full-scale reclaimed-water reverse osmosis system using adaptive control - Isnaeni Nurjanah; Mukhammad Jamaludin; Akhmad Azhar Firdaus; Wen-Hsiu Ku; Yi-Hsien Chiang; Chien-Ku Chen; Wu-Yang Sean (Process Safety and Environmental Protection, 2026)

Epidemiological study of Crimean- Congo haemorrhagic fever in Thi Qar (2023–2024): assessing the role of tick bites, household animals, slaughter and fresh meat exposure in disease transmission - Saja Abdalkadhum Hommod; Azhar kareem Razzaq; Ali B. Roomi (VirusDisease, 2026)

Upcycling Olive Mill Solid Waste into Lignin Nanoparticles for an Ecofriendly Soil Fertilization of Pomegranate - Azhar Ouni; Sahar ben Abdelwaheb; Samia Abboud; Rania Aydi Benabdallah; Mourad Jellali; Darine Tlili; Messaoud Mars; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2026)

Tagetes minuta L. Extract Ameliorates Epilepsy: Modulating Neuroinflammatory Pathways via Altering Brain-Derived Neurotropic Factor and Interleukin-6 Levels - Maryum Mumshad Raja; Humaira Naureen; Fawad Ali Shah; Sadia Adil; Arooj Mohsin Alvi; Rabia Khan; Sundas Safdar; Farah Azhar; Shahana Khattak (Journal of Pharmaceutical Innovation, 2026)

Agronomic and Edaphoclimatic Drivers of Pomegranate Fruit Quality: A Survey-Based Assessment - Azhar Ouni; Samia Abboud; Sahar ben Abdelwaheb; Soumaya Dbara; Messaoud Mars (Applied Fruit Science, 2026)

Integrative evidence on microplastics and heavy metals in vulnerable, threatened, and endangered species in natural environments: knowledge gaps, research priorities, and impacts - Hira Azhar; Noreen Khalid (Environmental Science and Pollution Research, 2026)

Evaluation of Alternaria alternata and A. tenuissima as novel entomopathogenic agents against Trogoderma granarium, Tribolium castaneum, and Rhyzopertha dominica - Tiyyabah Khan; Hafiz Azhar Ali Khan; Naeem Iqbal (Journal of Stored Products Research, 2026)

High-resolution HPLC-MS/MS profiling of group A and group B seed saponins in 711 diverse soybean germplasms - Adebabay Tazeb; Shengrui Zhang; Yanan Hou; Azhar Iqbal; Aimal Nawaz Khattak; Muhammad Ahsan; Emmanuel Kofi Sie; Jing Li; Bin Li; Junming Sun (Food Chemistry, 2026)

Fragile foundations: Why renewable energy (Not GDP) drives Somalia’s food security - Bile Abdisalan Nor; Azhar Mohamad (Food and Humanity, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Size-dependent impacts of polystyrene microplastics and heavy metals on soil microbiomes and spring onion (Allium fistulosum) health - Jazbia Shirin; Nazish Jabeen Abbasi; Syeda Anber Zahra; Azhar Hussain Shah; Qingye Sun; Qiyong Xu (Journal of Soils and Sediments, 2026)

Associations between handgrip strength, motor tasks, and quality of life in older adults with osteoarthritis - Asima Karim; Rizwan Qaisar; Firdos Ahmad; M. Azhar Hussain (European Journal of Applied Physiology, 2026)

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Multifaceted greenly synthesized ZnO-SnO2 core-shell heterojunctions for low-temperature optimized hydrogen generation and industrial pollutants remediation - Shamma Ayub; Abu Bakar Siddique; Azhar Abbas; Shoaib Akhtar; Faisal Sibtain; Nada K. Alharbi; Ashwag Shami; Esmael M. Alyami (Journal of Environmental Chemical Engineering, 2026)

High-entropy prussian blue analogue for rapid and efficient adsorptive removal of thallium from water: Performance and mechanism insights - Ying He; Changhao Cai; Yingming Ma; Azhar Mahmood; Zhenbang Liu; Wei Wang; Yu Bao; Zhonghui Sun; Li Niu; Carlos Ruiz Canovas; Dongxue Han; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2026)

Micromorphological assessment of pollen and foliar epidermal traits in Solanaceae using SEM characterization - Mehral Azhar; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Muhammad Rizwan Khan; Khuzin Dinislam; Nigar Mursal; Amna Shahid; Enkelejda Kucaj (The Science of Nature, 2026)

The beneficial effect of the soil treatment with hydrogen peroxide on a watermelon continuous cropping system is related to the reshaped soil microbiome - Yunfei Yu; Xiaoxue Li; Azhar Sohail Shahzad; Shunyao Zhuang (Applied Soil Ecology, 2026)

Carbon in above- and belowground harvest residues of silage maize under contrasting nutrient regimes - Azhar Zhartybayeva; Bent T. Christensen; Jørgen Eriksen; Axel Don; Johannes L. Jensen (Agriculture, Ecosystems & Environment, 2026)

Exploring the Role of Mitochondrial Sirtuin 3 Gene in Gastric Cancer Risk Based on SNP Analysis and LORD-Q Assay - Ishrat Mahjabeen; Muhammad Zahid Hussain; Maria Fazal-Ul Haq; Azhar Mehmood; Muhammad Shahbaz Haris; Shereen Ali Khan; Anum Chaudhry; Farzana Hakim; Ayesha Zulfiqar Abbasi; Mahmood Akhtar Kayani (Biochemical Genetics, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Integrated Mechanical–NDT Evaluation of Moisture- and Weathering-Induced Weakening in Granite, Marble, and Limestone Joints - Waqas Ahmed; Azhar Ali; Abdul Rahim Asif; M. E. Al-Atroush; Muhammad Yasir (Rock Mechanics and Rock Engineering, 2026)

Molecular adaptations of the estuarine fish Etroplus suratensis in response to salinity fluctuations - M. A. Pradeep; Saima Rehman; Irine Maria Jose; T. V. Arun Kumar; Vinaya Kumar Katneni; Adnan Hussain Gora; N. R. Dhanutha; Ashok Kumar Jangam; T. S. Azhar Shahansha; K. K. Vijayan (Frontiers in Marine Science, 2026)
Climate-driven shifts in salinity regimes pose significant challenges to aquatic organisms, particularly those inhabiting dynamic coastal ecosystems. Etroplus suratensis (Pearl spot), a euryhaline cichlid capable of thriving across fresh, brackish, and marine environments, offers an excellent model for understanding molecular strategies underpinning salinity acclimation. This study investigated the transcriptomic reprogramming in the gills of fish acclimated for 21 days to freshwater (0‰), brackish water (18‰), and marine water (36‰) conditions. Freshwater exposure elicited a coordinated metabolic response characterized by activation of mitochondrial energy pathways, including oxidative phosphorylation and electron transport, to support ATP-intensive ion uptake, alongside enhanced ion transport functions and epithelial remodeling. In contrast, marine water exposure triggered a more pronounced osmoregulatory shift, with activation of calcium-dependent exocytosis and vesicular trafficking pathways central to maintaining ion balance under high salinity. However, prolonged marine water exposure also led to suppression of key antioxidant and immune pathways, revealing a potential trade-off whereby resources are redirected toward ion regulation at the expense of physiological defense mechanisms. Concurrent enrichment of cortisol synthesis, autophagy, apoptosis, and other stress-responsive pathways further reflects cellular remodeling and adaptive stress management under salinity stress. Collectively, these results demonstrate the remarkable metabolic plasticity and molecular resilience of E. suratensis , highlighting its capacity to deploy distinct, context-dependent mechanisms to maintain homeostasis across fluctuating salinity environments.

Microplastic exposure reduces multi-trophic biomass yield in a freshwater integrated aquaculture system - Gökhan Tunçelli; Muhammad Hanif Azhar; Devrim Memiş; Nuray Erkan; Idil Can-Tuncelli; Özkan Özden; Eda Dagsuyu; İsmet Burcu Turkyilmaz Mutlu; Refiye Yanardag (Aquaculture International, 2026)
Freshwater integrated multi-trophic aquaculture (IMTA) systems are increasingly used to enhance nutrient utilization efficiency; however, their performance under microplastic (MP) exposure remains poorly characterized. This study evaluated the effects of water-borne and feed-borne polyethylene (PE) MP (10–20 µm) on biomass production and filtration performance in a three-compartment freshwater IMTA system comprising rainbow trout ( Oncorhynchus mykiss ), freshwater mussels (Unionidae), and duckweed ( Lemna minor ). Fluorescent spherical MPs were applied in four treatments ( n = 3 tanks per treatment): control (no MPs), feed-borne MPs (5 particles per 100 g feed), water-borne MPs (35 particles L⁻ 1 at fish-tank inflow), and combined exposure. The exposure phase lasted 45 days with 15-day sampling intervals, followed by a 45-day depuration phase. Fish growth responses differed modestly among treatments during exposure, with transient reductions observed in MP-exposed groups relative to the control at intermediate sampling points. Mussel filtration capacity showed limited variation among treatments, with no consistent treatment-specific suppression across time. Duckweed biomass accumulation was lower under combined exposure compared with the control, whereas variability was higher in MP treatments during early growth stages. An integrated multi-trophic performance index calculated from terminal measurements indicated moderate reductions in overall system productivity under combined exposure relative to the control. During depuration, growth trajectories across treatments converged. These results indicate that elevated microplastic exposure can influence biomass distribution and productivity within freshwater IMTA systems, particularly under combined exposure scenarios.

Bacillus velezensis ATC-AL suppresses mycotoxin-producing fungi by disrupting membrane integrity and inducing mitochondrial dysfunction - Yuerong Zhang; Kewei Hua; Benni Ma; Chen Yang; Panpan Zhu; Bingqian Hu; Humana Azhar; Qingru Geng; Fengqin Song; Jun Tian; Kunlong Yang (Physiological and Molecular Plant Pathology, 2026)

Vitamin D supplementation and its role in modulating ovarian reserve and oxidative stress in infertile females - Arfa Azhar; Syed Mahboob Alam; Faiza Alam; Fatima Abid; Aysha Habib; Rehana Rehman (PharmaNutrition, 2026)

Artificial intelligence and machine learning in postharvest fruit quality assessment: Current challenges, recent advances, and future prospects - M.J. Gidado; Ahmad Anas Nagoor Gunny; Subash C.B. Gopinath; Monisha Devi; Azhar Mohd Ibrahim (Journal of Stored Products Research, 2026)

Exploring patterns and mechanisms of indigenous microbial community succession driven by polycyclic aromatics in heterotrophic nitrification and aerobic denitrification systems - Weidong Xiao; Yaoguo Wu; Lang Ran; Ran Sun; Sihai Hu; Zherui Zhang; Usman Ghani; Azhar Masaud; Maorui Zhang (Bioresource Technology, 2026)

Multigenerational exposure to the fungicide tebuconazole reveals hormetic effects on the demography and biology of a non-target vector mosquito Aedes albopictus - Hafiz Azhar Ali Khan; Tiyyabah Khan (Aquatic Toxicology, 2026)

Barcoding and genetic variation in Eutyphoeus species (Crassiclitellata: Acanthodrilidae) with first report of E. pharpingianus (Michaelsen 1907) from Mizoram, North Eastern Region (NER) of India - Azhar Rashid Lone; Samrendra Singh Thakur; Pooja Tiwari; Samuel Wooster James; Shweta Yadav (The Nucleus, 2026)

Quercetin as a promising HIS-C inhibitor and novel therapeutic against antibacterial drug-resistant Acinetobacter baumannii: in vitro and in silico insights - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Safaa A. Turkistani; Ahmed Afandi; Abdulaziz A. Kimawi; Samah O. Noor; Adhari Alselmi; Salma Mohammed Alsayed; Mada S. Alharthi; Vivek Dhar Dwivedi; Pradeep Sharma; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Minimum tension reinforcement ratio for beams made of pumice aggregate lightweight concrete - Azad A. Mohammed; Azhar J. Nimat (Innovative Infrastructure Solutions, 2026)

Molecular identification and phylogenetic analysis of four viruses infecting shallot in Java Island, Indonesia - Siska Nur Siti Yuliandini; Alif Lammim Al Azhar; Dyana Rahma Ningrum; Paramita Maris; Sari Nurulita; Mahmoud A. Amer; Adyatma Irawan Santosa (Indian Phytopathology, 2026)

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Secondary tree crops boost butterfly diversity and abundance in oil palm alley-cropping systems - Mohamad Ashraf; Tetsuro Hosaka; Badrul Azhar; Ahmad R. Norhisham; Ruzana Sanusi; Miyabi Nakabayashi; Ramle Moslim; Raja Zulkifli; Kamil A. Tohiran (Agroforestry Systems, 2026)

Towards Trustworthy Artificial Intelligence for Marine Research, Fisheries and Environmental Management - Jose A. Fernandes‐Salvador; Angel Borja; Asier Anabitarte; Igor Granado; Xabier Lekunberri; Yolanda Sagarminaga; Oriol Canals; Anders Lanzen; Mihailo Azhar; Jonne Kotta; Henn Ojaveer; Anna Spinosa; et al. (Fish and Fisheries, 2026)
Artificial Intelligence (AI) is advancing at an unprecedented pace, offering transformative opportunities for marine research, fisheries management, environmental governance and policy development. Particularly in the context of the interconnected data needs of ecosystem management and biodiversity conservation, these technologies can enhance data acquisition, processing and decision support, enabling more integrated approaches to ecosystem management and biodiversity conservation. Yet their adoption in these domains remains limited by the absence of coherent frameworks that ensure transparency, validation and ethical alignment with ecological and socio‐economic sustainability goals. This work proposes a comprehensive framework built on three critical pillars for trustworthy AI: socio‐economic and legal viability, data governance and technical and scientific robustness. On the one hand it aims to be a guideline for developer teams. On the other hand, it aims to be a guideline for final users (e.g., industry and managers) for designing the requirements and evaluating such systems. The first pillar underscores the need for AI systems that are cost‐effective, scalable, environmentally sustainable and legally supported, balancing short‐term costs with long‐term social and ecological benefits. The second stresses adherence to fair, reliable and ethical access to digital resources, recognising that without strong governance data and algorithms risk becoming fragmented or misused. The third pillar addresses the necessity of rigorous validation across entire AI pipelines, including preprocessing, model evaluation and benchmarking against alternative ground truths, to ensure reliability in real‐world applications. Together, these pillars provide a blueprint for developing ethical, reliable and policy‐relevant AI systems that can strengthen trust, improve sustainability and guide decision‐making across marine science, fisheries, environmental management and European legislation.

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Toxicity and sublethal effects of fluralaner on the development of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Hafiz Azhar Ali Khan; Tiyyabah Khan (Crop Protection, 2026)

0D/2D S-scheme NFCN/ZIS heterojunction with ultrafast electron transfer and enhanced photocatalytic performance - Hao Xu; Ke Liu; Chunfang Deng; Azhar Ayyub; Yanming Zhou; Zhenyu Wan; Wei Yuan; Yulong Yao; Krongthong Kamonsuangkasem; Meisong Xu; Wei Zheng; Hongxiao Zu; et al. (Journal of Environmental Chemical Engineering, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Vertical growth of ZnIn2S4 on Sr2MgSi2O7:Eu2+, Dy3+ boosts surface area and covalent S-scheme charge separation for round-the-clock photocatalytic degradation of organic pollutants - Chunfang Deng; Hao Xu; Yanming Zhou; Azhar Ayyub; Zhenyu Wan; Wei Yuan; Yulong Yao; Krongthong Kamonsuangkasem; Wei Zheng; Meisong Xu; Sibudjing Kawi; Wanliang Yang (Journal of Environmental Chemical Engineering, 2026)

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Salt stress mitigation in pomegranate using olive mill solid waste derived phenolic extract - Sahar Ben Abdelwaheb; Samia Abboud; Azhar Ouni; Darine Tlili; Mourad Jellali; Amani Bchir; Noomene Sleimi; Soumaya Dbara (Biocatalysis and Agricultural Biotechnology, 2026)

Lariciresinol: a potent natural compound with diverse therapeutic and health benefits - Ijaz Hussain; Azhar Rasul; Mudassir Hassan; Ravi Rawat; Yusuf Tutar (Natural Product Research, 2026)

Unveiling the bee pollinators interaction with Muntingia calabura: implications for urban biodiversity conservation in tropical cityscapes - Muhammad Syafiq Yahya; Nuur Farhani Zulkifli; Sharifah Nur Atikah; Ruzana Sanusi; Badrul Azhar; Ahmad Razi Norhisham (Journal of Insect Conservation, 2026)

Anti-arthritic effect of Helicteres isora L. ethanolic extract via modulation of cytokines and oxidative stress in CFA-induced arthritic rats - Muhammad Muzammil Nazir; Azhar Rafique; Salma Sultana; Asma Ashraf (Inflammopharmacology, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Retraction Note: The impact of COVID-19 on the sustainability of the environment, animal health and food security, and safety - Ibrahim H. Alshubaith; Salah Alhajri; Ahlam Alhajri; Raed A. Alsultan; Esam I. Azhar; Bakr Hussain Alhussaini; Lafi S. Al Solami; Maria Cristina de Oliveira; Asmaa F. Khafaga; Adel D. Alqurashi; Youssef A. Attia (Environmental Science and Pollution Research, 2026)

Active fault map and paleoseismology results from the Aceh Fault in North Sumatra, Indonesia: Unravelling faulting dynamics along the Great Sumatran Fault system - Gayatri Indah Marliyani; Yann Klinger; Aulia Kurnia Hady; Agung Setianto; Wenqian Yao; Hurien Helmi; Telly Kurniawan; Retno Agung Prasetyo Kambali; Zulham Sugito; Abdi Jihad; Yosi Setiawan; Andi Azhar Rusdin; et al. (Tectonophysics, 2026)

Surface rupture signatures of historical earthquakes (16th and 19th centuries) from Kumaon-Garhwal, central Himalaya: Implications for seismic hazard assessment - Javed N. Malik; Mitthu Dhali; Mahendrasinh S. Gadhavi; Prabhat Kumar; Eshaan Srivastava; Mohd Azhar Ansari; Nayan Sharma; Santiswarup Sahoo; Pankaj Kumar (Journal of Structural Geology, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Emerging contaminants and their influence on plants: An in-depth review - Sadia Aziz; Sania Zaib; Azhar Iqbal; Muhammad Asif Chuadhry; Shaheen Shahzad; Bikram Dhara; Athanasios Alexiou; Partha Biswas; Mohamed M. Abdel-Daim; Shabana Bibi (Environmental Toxicology and Pharmacology, 2026)

Surface self-reconstruction of metal oxychalcogenide cluster activating lattice oxygen to catalyze oxygen evolution - Bolin Zhao; Rana Muhammad Irfan; Azhar Mahmood; Shamraiz Hussain Talib; Chuhao Liu; Li Niu (Chemical Engineering Journal, 2026)

Mitigating radioresistance mechanisms by polymer-lipid manganese dioxide nanoparticles enhances immunogenic cell death and antitumor immune response to facilitate abscopal effect in breast tumor models - HoYin Lip; Abdulmottaleb Zetrini; Elliya Park; Ping Cai; Azhar Z. Abbasi; Ting Huyan; Ibrahim Alradwan; Andrew M. Rauth; Xiao Yu Wu (Drug Delivery and Translational Research, 2026)

Alien floral homogenizes the traditional knowledge diversity of isolated ethnic communities - Nausheen Niaz; Shiekh Marifatul Haq; Aadil Abdullah Khoja; Muhammad Waheed; Muhammad Azhar Jameel; Manzer H. Siddiqui; Ivana Vitasović-Kosić; Rainer W. Bussmann (Biological Invasions, 2026)

Clostridium botulinum serotype B: microbial genetics, toxin biosynthesis, current applications, and future prospects - Aditi Kulshreshtha; Sataditya Jana; Ritika Rana; Azhar Khan (Archives of Microbiology, 2026)

Fluorescence Interface Engineering of PEDOT: PSS–HTL and BPhen–ETL Layers in Alq₃-Based OLEDs for Biomedical Applications - Ghazi Aman Nowsherwan; Hafiz Muhammad Khubaib; Muhammad Azhar; Saira Riaz; Shahzad Naseem (Journal of Fluorescence, 2025)

Habitat requirement analyses can guide pest rodent management in oil palm plantations: Evidence from Sabah, Malaysia - Nur Athirah Asrif; Mohd Noor Hafidzi; Maisarah Burhanuddin; Badrul Azhar (Crop Protection, 2025)

Integrated Chitosan-based coagulation and microbubble pre-treatment for improved microplastic fibre removal from water - Nimesha Thathsarani; Mohadeseh Najafi; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Science of The Total Environment, 2025)

Potential novel biomarkers for gestational diabetes mellitus in first and early second trimesters: A comprehensive review - Rabail Azhar Iqbal; Sophia Nazir (Reproductive Biology, 2025)

Corrigendum to “Cytocompatible and non-fouling zwitterionic hyaluronic acid-based hydrogels using thiol-ene ‘click’ chemistry for cell encapsulation” [Carbohydrate Polymers 236 (2020) 116021] - Yabin Zhang; Shuyan Liu; Tianyu Li; Luqing Zhang; Umair Azhar; Jiachen Ma; Congcong Zhai; Chuanyong Zong; Shuxiang Zhang (Carbohydrate Polymers, 2025)

From pollutant to soil input: Phytotoxicity and physicochemical profiling of olive mill residues for safe agriculture reuse - Samia Abboud; Sahar Ben Abdelwaheb; Darine Tlili; Azhar Ouni; Mourad Jellali; Karim Lahmar; Rania Aydi Ben Abdallah; Nour Sghaier; Soumaya Dbara (Bioresource Technology Reports, 2025)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Mechanistic insight into nanomedicine for polycystic ovary syndrome - Maisra Azhar Butt; Sobia Tabassum; Rowan S Hardy; Mubin Mustafa Kiyani (Molecular Biology Reports, 2025)

Identifying the Worthy and Compatible Excipients Through In-Silico Approach for Rational Formulation Development: Insights into the Acyclovir and Trimethoprim Formulations - Abhijeet H. Patil; Meera C. Singh; Mohammed Sakib Musa; Minhaz Abdullah Al Mueid; Hossain Mohammed Reza; Md. Eshak Enan; Mahadie Hasan Jahad; Jamil Azhar Shakil; Shibam Mondal; Rajesh B. Patil (Journal of Pharmaceutical Innovation, 2025)

Sustainable integrated oil-palm livestock practice to enhance soil organic matter and carbon sequestration potential - Y. Umar; K. Sayed; M. I. Syakir; T. K. Al-Saedi; B. Azhar; K. A. Tohiran; F. Nobilly (International Journal of Environmental Science and Technology, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

Isolation and characterization of biosurfactant-producing bacteria from the Thar Desert - Samrendra Singh Thakur; Azhar Rashid Lone; Anisa Ratnasari; Stefany Solano González; Subodh Kumar Jain (Antonie van Leeuwenhoek, 2025)

From source to stream: CEC source identification and quantification in the Changle River Watershed - Meixian Cao; Dan Qin; Xin Liao; Qiaoting Zeng; Yiqing Zhang; Azhar Rashid; Anyi Hu; Chang-Ping Yu; Qian Sun (Journal of Hazardous Materials, 2025)

Deciphering the role of non-covalent interactions in CO2 Capture: A DFT and COSMO-RS study of amino acid-based ionic liquids - Hira Karim; Sabahat Sardar; Suhan Prasantha Panditharatne; Asad Mumtaz; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Management, 2025)

Harnessing the power of amphoterically modified Chitosan coagulants for enhanced Polyester microplastic fibre removal from water - Nimesha Thathsarani; Mohadeseh Najafi; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Journal of Environmental Management, 2025)

Enhancing maize grain nutritional quality through combined application of Zn-enriched compost and rhizobacteria under natural arid conditions - Zafar Iqbal; Azhar Hussain; Maqshoof Ahmad; Abubakar Dar; Moazzam Jamil; Usman Zulfiqar; Hossam S. El-Beltagi; Muneera A. Saleh; P.V. Vara Prasad; Ivica Djalovic (Journal of Cereal Science, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Alien flora of the Kingdom of Saudi Arabia: taxonomic composition, phylogenetic patterns, and invasion status - Shiekh Marifatul Haq; Muhammad Waheed; Muhammad Azhar Jameel; Łukasz Walas; M. Nasir Khan; Manzer H. Siddiqui; Saud Alamri; Anas E. AbuYahya; Rainer W. Bussmann (Biological Invasions, 2025)

Characterization of ambient air quality and its relationship with respiratory morbidity in typical cities of Northwest China (NWC) - Shah Zaib; Jianjiang Lu; Gao Yan; Xiaowen Yin; Xiaoning Lei; Muhammad Zeeshaan Shahid; Azhar Siddique; Mariam A. Yousaf Al-Nesf (Air Quality, Atmosphere & Health, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

The nexus between global value chains and productivity gains of ASEAN countries - Zia Ur Rahman; Wajid Khan; Musarat Abbas; Fatima Gulzar; Muhammad Azhar Farooq (Environment, Development and Sustainability, 2025)

Seasonal trends and source apportionment of water-soluble inorganic ions in PM2.5 in Makkah, Saudi Arabia - Yousef Alsufayan; Shedrack R. Nayebare; Omar S. Aburizaiza; Azhar Siddique; David O. Carpenter; Mirza M. Hussain; Jahan Zeb; Abdullah J. Aburiziza; Haider A. Khwaja (Science of The Total Environment, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Soft sensing of biological oxygen demand in industrial wastewater using machine learning models - Muhammad Hassnain; Sarada M.W. Lee; Muhammad Rizwan Azhar (Journal of Water Process Engineering, 2025)

Spatial non-targeted screening and machine learning-based risk assessment of organic pollutants in honey from Bhakkar District, Pakistan - Mahnoor Baloch; Abrar Hussain; Syed Kumail Hussain Naqvi; Khurram Shahzad; Khaled Chawraba; Tahir Mehmood; Azhar Mahmood; Sang Hyun Park (Journal of Environmental Chemical Engineering, 2025)

Requirements for a food traceability system in a fruit supply chain - Azhar Cader; Anton H. Basson; Karel Kruger; Nicole C. Taylor (Food Control, 2025)

Sustainable passive design in cold regions: energy and thermal evaluation of traditional Zhuangke dwellings — in Qinghai Province, China - Yunfei Liu; Muhamad Azhar Ghazali; Linjie Yang; You Chen (Energy and Buildings, 2025)

Ferroptosis: a novel pathway in the pathogenesis and treatment of endometriosis - Xunshu Cheng; Muhammad Azhar Memon; Waseem Ali; Yonggang Ma (Journal of Molecular Histology, 2025)

Integration of multivariate indices to correlate pollen morphology and evolutionary adaptations in halophytes - Moona Nazish; Asif Kamal; Muhammad Azhar Khan; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Fozia Bibi; Jawaher Alkahtani; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Evaluating the therapeutic qualities of community parks: An elderly-centric perspective - Xinyu Lin; Wardah Fatimah Mohammad Yusoff; Mohd Khairul Azhar Mat Sulaiman (Urban Forestry & Urban Greening, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Biocontrol potential of isolates of Aspergillus flavus and Aspergillus parasiticus against Rhyzopertha dominica, Trogoderma granarium, and Tribolium castaneum - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Journal of Stored Products Research, 2025)

Influence of temperature and relative humidity on the combined efficacy of insecticides and diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

Microbial fuel cells, macropore, and farm-oriented enhancing aquatic systems: Evaluating their impact on redox potential and greenhouse gas emissions in paddy soils - Adhia Azhar Fauzan; Komariah; Takeo Onishi; Ken Hiramatsu (Journal of Environmental Management, 2025)

A comprehensive review on the recovery of lithium from lithium-ion batteries and spodumene - Asad Ali; Sadia Afrin; Abdul Hannan Asif; Yasir Arafat; Muhammad Rizwan Azhar (Journal of Environmental Management, 2025)

Cinnamon bark oil application and modified atmosphere packaging alleviates chilling injury, ethylene production and maintains antioxidant system in persimmons - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Muhammad Rizwan Azhar; Eben Afrifa-Yamoah; Andrew Woodward (Food Chemistry, 2025)

Rapid prototyping of 3D-printed microchannel heat exchangers via AI-driven design and optimization - Amirreza Mottafegh; Azhar Rohimmahtunnissa; Dong-Pyo Kim (Chemical Engineering Journal, 2025)

Expression Profiling of Genome-Wide Identified and Characterized Trans-Isoprenyl Diphosphate Synthase Family in Catharanthus roseus (L.) G. Don Under Stress Conditions - Muhammad Huzafa; Amjad Hassan; Batool Bashir; Azhar Mehmood; Jawad Ahmed (Plant Molecular Biology Reporter, 2025)

Meta-analysis of soil oxygen distribution: plant species-specific dynamics and optimal levels for plant growth - Weiwei Zhang; Jianshuang Gao; Azhar Sohail Shahzad; Shunyao Zhuang (Plant and Soil, 2025)

Biostratigraphy, Microfacies, and Palaeoenvironmental Dynamics of the Early Eocene Dungan Formation, Pakistan: implications for the Carbonate Ramp Evolution and Larger Foraminiferal Extinction and Origination Event (LFEO) during Global Warming - Muhammad Azhar Farooq Swati; Muhammad Hanif (Carbonates and Evaporites, 2025)

A comparative analysis of diamond nanoparticles prepared by pulsed laser for antibacterial application against Streptococcus mutans - Fattin A. Fadhil; Ahlam Taha Mohammed; Azhar M. Haleem; Abdulrahman Khalaf Ali (Toxicology and Environmental Health Sciences, 2025)

N-AquaRAM: A Cost-Efficient Deep Learning Accelerator for Real-Time Aquaponic Monitoring - Ali Siddique; Muhammad Azhar Iqbal; Jingqi Sun; Xu Zhang; Mang I. Vai; Sunbal Siddique (Agricultural Research, 2025)
Aquaponics is an emerging area of agricultural sciences that combines aquaculture and hydroponics in a symbiotic way to increase crop production. Though it offers a lot of advantages over traditional techniques, including chemical-free and soil-less farming, its commercial application suffers from some problems such as the lack of experienced manpower. To operate a stable smart aquaponic system, it is critical to estimate the fish size properly. In this context, the use of dedicated hardware for real-time aquaponic monitoring can greatly resolve the issue of inexperienced handlers. In this article, we present a complete methodology to train a deep neural network to perform fish size estimation in real time. To achieve high accuracy, a novel implementation of swish function is presented. This novel version is far more hardware efficient than the original one, while being extremely accurate. Moreover, we present a deep learning accelerator that can classify 40 million fish samples in a second. The dedicated real-time system is about 1600 times faster than the one based on general-purpose computers. The proposed neuromorphic accelerator consumes about 2600 slice registers on a low-end model of Virtex 6 FPGA series.

Genomic analysis and spatiotemporal distribution of newly emerging lumpy skin disease virus in malaysia identify recombinant strain from transboundary spread - Nurain Izzati Saidi; Nur Athirah Azhar; Mohamad Azlan Jahaya; Mohd. Shafarin Shamsuddin; Syahrol Zamzuri (The Veterinary Journal, 2025)

Controlled electrochemical design of activated carbon surface chemistry: Enhanced copper recovery using functionalized walnut shell-derived sorbents - Dinara Abduakhytova; Saken Abdimomyn; Azhar Atchabarova; Mojtaba Mirzaeian; Rustam Tokpayev; Askar Mukanov; Graziella Liana Turdean; Fyodor Malchik; Mikhail Nauryzbayev (Journal of Water Process Engineering, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Enhancing soil quality and economic value in oil palm plantations: Effects of livestock integration on earthworm abundance and ecosystem services - Thaer Kareem Al-Saedi; Khalid Sayed; M.I. Syakir; Yarima Umar; Badrul Azhar; Kamil A. Tohiran; Frisco Nobilly; Siti Rahyla Rahmat (Journal for Nature Conservation, 2025)

Machine learning, network pharmacology, and molecular dynamics reveal potent cyclopeptide inhibitors against dengue virus proteins - Mohammed A. Imam; Thamir A. Alandijany; Hashim R. Felemban; Roba M. Attar; Arwa A. Faizo; Hattan S. Gattan; Vivek Dhar Dwivedi; Esam I. Azhar (Molecular Diversity, 2025)

Formulation of Mixed Micelles of Various Model Drug Ionic Complexes in an Optimized Micellar Base Composed of Surfactants and Cosolvent Mixture: In Vitro Analysis of Drug Delivery Efficiency - Ahmad Saleh Malkawi; Collins Ovenseri Airemwen; Azhar Malkawi (Journal of Pharmaceutical Innovation, 2025)

Investigation of geoenvironmental contamination and risks of municipal solid waste disposal sites in urban Khyber Pakhtunkhwa, Pakistan - Muhammad Ayaz Khan; Abdullah Khan; Zia ur Rahman; Azhar Rashid; Khalid Latif (Environmental Geochemistry and Health, 2025)

Endophytic fungus from Gynura japonica : phytochemical screening, biological activities, and characterisation of its bioactive compound - Riga Riga; Ridha Wardatillah; Okta Suryani; Benny Ryplida; Suryelita Suryelita; Minda Azhar; Dian Handayani; Muh. Ade Artasasta; Sonni Maurit Benu; Ahadul Putra (Natural Product Research, 2025)

Negative influence of suboptimal quality of drinking water on avian coronavirus pathogenesis and immune response: A Controlled Study - Muhammad Farooq; Awais Ghaffar; Ahmed Ali; Ryan Rahimi; Muhammad Azhar; Ishara M. Isham; Heshanthi Herath-Mudiyanselage; Sufna M. Suhail; Mohamed Faizal Abdul-Careem (Veterinary Immunology and Immunopathology, 2025)

Assessing stakeholder awareness and perceptions of equity in communicating extreme weather risks to communities - Mohammed Azhar; Saeed Rokooei; Julian Kelly; Hannaneh A. Rashidi; Reza Khanbilvardi; Kaveh Madani; Farshid Vahedifard (Sustainable Cities and Society, 2025)

Linking government support, and quality management with sustainable energy project success: mediating role of community participation and moderating role of project governance - Shahid Hussain; Tasawar Baig; Saadia Beg; Azhar Ali (Innovative Infrastructure Solutions, 2025)

The environmental impacts via life cycle assessment of activated carbon produced by Fiddlewood and Jacaranda biomass - Muhammad Amin; Hamad Hussain Shah; Muhammad Usman; Muhammad Azhar Iqbal (Clean Technologies and Environmental Policy, 2025)

Dual colorimetric sensing of Hg(II) and Fe(III) using sulfanilamide-stabilized silver nanoparticles and evaluating their photodegradation and antibacterial properties - Maria Kanwal; Muhammad Sher; Azhar Abbas; Shoaib Akhtar; Abu Bakar Siddique; Muhammad Naeem ul Hasan; Nasir Assad; Hassan A. Alhazmi; Hatem M.A. Amin (Journal of Water Process Engineering, 2025)

Enhanced removal of microplastic fibres using aluminium and chitosan-based coagulants assisted with microbubble technology - Nimesha Thathsarani; Mehdi Khiadani; Muhammad Rizwan Azhar; Masoumeh Zargar (Journal of Environmental Chemical Engineering, 2025)

Ameliorating the deleterious effect of water deficit stress on pomegranate through soil application of polyphenols-enriched extract from olive mill solid wastes - Samia Abboud; Darine Tlili; Azhar Ouni; Sahar Ben Abdelwaheb; Karim Lahmar; Mourad Jellali; Nour Sghaier; Rania Aydi Ben Abdallah; Soumaya Dbara (Journal of Environmental Chemical Engineering, 2025)

Unravelling the role of non-covalent interactions using imidazolium and amino acid based organic salts for efficient CO2 capture: experimental, DFT and COSMO-RS explorations - Hira Karim; Sabahat Sardar; Asad Mumtaz; Anila Tabassum; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Cecilia Devi Wilfred; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2025)

Carissa macrocarpa Extract Based Greenly Synthesized AuNPs: A Sustainable Approach for Lead Ion Detection, Azo Dye Degradation, and Antimicrobial Applications - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Mamoon Ur Rasheed; Abdul Karim; Muhammad Mustaqeem; Muhammad Fayyaz ur Rehman; Mohammad Mahtab Alam; Amirah S. Alahmari (Water, Air, & Soil Pollution, 2025)

Molecular and genetic analysis of methicillin-resistant Staphylococcus aureus (MRSA) in a tertiary care hospital in Saudi Arabia - Mohd Saleem; Irfan Ahmad; Alharbi Mohammed Salem; Sumayyah Mohammad Almarshedy; Soha Abdallah Moursi; Azharuddin Sajid Syed Khaja; Ehab Rakha; Asim Azhar; Metab Nasser Ashammari; Homoud Almalaq; Kareemah Alshurtan; Mohd Shahid Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dynamics of bi-susceptibility patterns in Covid-19 outbreaks and associated abstain strategies - Waheed Ahmad; Muhammad Rafiq; Azhar Iqbal Kashif Butt; Momina Zainab; Naeed Ahmad (Modeling Earth Systems and Environment, 2025)

Genome-wide identification and characterization of light-responsive FAR1 gene family in finger millet (Eleusine coracana) under abiotic stress - Urooba Abid; Azhar Iqbal; Mahnoor Mazher; Shabana Bibi; Sara Ashraf; Mohamed Kamel; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Muhammad Sajid (Genetic Resources and Crop Evolution, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Energy bandgap tuning of Sr-doped ZnO nanoparticles for photodegradation of azo dyes and antibacterial applications - Hufsa Ahmad; Abu Bakar Siddique; Saima Zaheer; Rabia Sattar; Azhar Abbas; Muhammad Amin; Rashad Al-Salahi; Hatem A. Abuelizz; M. Zubair Saleem (Journal of Water Process Engineering, 2025)

Effectiveness of pirimiphos-methyl, alpha-cypermethrin, spinetoram and thiamethoxam alone and in combination with diatomaceous earth for the control of Trogoderma granarium on rough rice - Muhammad Bukhari; Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2025)

A parametric study of particle size influence on sewage sludge-derived hydrochar and coal char co-gasification: Reactivity and carbon conversion analysis - Azhar Ali Laghari; Asma Leghari; Akash Kumar; Lata Kumari; Muhammad Rizwan; Qurat-ul-ain Abro; Memon Kashif Ali; Yongheng Shen; Qingxia Guo (Biomass and Bioenergy, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Impacts of climate change on Pakistan’s weather patterns: a comprehensive study of temperature and precipitation trends - Hafiza Nida; Muhammad Kashif; Azhar Ali Janjua; Muhammad Aslam; Kamil Shahzad Cheema; Sami Ullah (Environmental Monitoring and Assessment, 2025)

Foam-Based Drug Delivery Systems for Skin Disorders: A Comprehensive Review - Syrsulu Myrzagulova; Zhexenova Azhar N; Mohit Kumar; Devesh Kumar; Akshay Kumar (AAPS PharmSciTech, 2025)

Sublethal and hormetic effects of the fungicide tebuconazol on the biology of a nontarget pest insect, Musca domestica - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Science of The Total Environment, 2025)

Unveiling challenges of aluminium electrode fouling and passivation in electrocoagulation treatment system for sustainable water management of coastal Borneo peatlands: A focused review - Nazeri Abdul Rahman; Calvin Jose Jol; Allene Albania Linus; Siti Noor Linda Taib; Arif Parabi; Chieng Kwong Ming; Astisza Syahla Ludmilla Parabi; Anthonette James; Nur Syazwa Samsol; Sebastian Belun John; Airul Azhar Jitai; Dayang Fadhilatul Aishah Abang Abdul Hamid (Environmental Research, 2025)

Impact of mesh resolutions for reproducing wind gustiness and probability distribution at pedestrian levels for a simplified block array - Haitham Osman; Wei Wang; Muhd Azhar bin Zainol; Naoki Ikegaya (Building and Environment, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Spatial patterns of colorectal cancer survival rates in Malaysia, 2013–2018 - Siti Ramizah Ramli; Zahir Izuan Azhar; Sukumaran Raman; Siti Norbayah Yusof; Mariam Mohamad (Cancer Causes & Control, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Cardiac-specific overexpression of serum response factor regulates age-associated decline in mitochondrial function - Pankaj Patyal; Gohar Azhar; Xiaomin Zhang; Ambika Verma; Jeanne Y. Wei (GeroScience, 2025)
Cardiac aging is an intrinsic process that leads to impaired heart function, along with cellular and molecular changes. Recent research highlights the important role of mitochondria in cardiac function, due to the heart's high energy demands. Serum response factor (SRF), a transcription factor involved in regulating actin and smooth muscle gene expression, is well known as a regulator of various aspects of cardiac function. However, its role in mitochondrial regulation and cardiac aging is poorly understood. Our laboratory generated a transgenic mouse model with cardiac-specific overexpression of SRF, which exhibits characteristics of diastolic dysfunction and accelerated cardiac aging in young adult transgenic mice. In this study, we tested how cardiac-specific overexpression of SRF affects age associated mitochondrial dysfunction in the heart. Our results showed that cardiac specific SRF overexpression reduced the lifespan of mice and induced cardiomyopathy. Histological analysis revealed cardiac hypertrophy and fibrosis in transgenic mice hearts. SRF overexpression led to significant alterations in mitochondrial structure and function, including reduced mitochondrial biogenesis and dysregulation of oxidative phosphorylation. These changes were accompanied by increased oxidative stress, a decline in antioxidant enzyme activity, and disrupted calcium handling. Moreover, cardiac-specific SRF overexpression activated the MAPK signaling pathway. Our findings were further corroborated by similar mitochondrial dysfunction observed in a human cardiomyocyte cells transfected with SRF plasmid. Taken together, these findings suggest that SRF plays a novel role in cardiac aging, thus establishing SRF as a potential therapeutic target for mitigating age-associated decline in mitochondrial function and preserving cardiac health in older adults.

An integrated approach to understanding Corvus splendens’ invasive behaviour, genetic dynamics, and ecological impact for its strategic management - Mazen M Jamil Al-Obaidi; Zakiya Al Afifi; Nurul Diana Dzaraly; AbdulRahman Muthanna; Mohd Nasir Mohd Desa; Mohd Nizam Lani; Qais AlRawahi; Suleiman AlAkzami; Rahma Al-Nadhairi; Ahmed Al-Shukaili; Zeyana Al-Omairi; Mohammed Akak; et al. (Biologia, 2025)

Overcoming aminoglycoside antibiotic resistance in Mycobacterium tuberculosis by targeting Eis protein - Geethu S. Kumar; Kuldeep Sharma; Richa Mishra; Esam Ibraheem Azhar; Vivek Dhar Dwivedi; Sharad Agrawal (In Silico Pharmacology, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Impact of various tea infusions on the cooking, texture, and microstructure of fresh white salted noodles - Hui-Ling Tan; Kok-Cheong Yong; Thuan-Chew Tan; Azhar Mat Easa (International Journal of Gastronomy and Food Science, 2025)

Tree abundance and elevation influence the occurrence of limestone hill forest-dwelling stump-tailed macaques (Macaca arctoides) in northern Peninsular Malaysia - Petra Sulai; Tee Sze Ling; Amal Ghazali; Abd Rahman Syamil; Afiq Amran; Alex Lechner; Badrul Azhar (Journal for Nature Conservation, 2025)

Spatial distribution patterns, hotspots of contaminants of emerging concern and driving factors in a river network of Xizang Plateau - Qiaoting Zeng; Azhar Rashid; Meixian Cao; Yanwen Jia; Keshao Liu; Anyi Hu; Lanping Zhang; Qian Sun (Environmental Research, 2025)

Satellite based assessment of potential fishing zones (PFZs) within the exclusive economic zone (EEZ) of Pakistan - Atifa Nadeem; Asim Daud Rana; Syeda Adila Batool; Zia ul-Haq; Ayesha Azhar; Ushna Bint E Ishfaq; Ammar Hameed (Continental Shelf Research, 2025)

Molecular diversity and phylogenetic analysis of ten sheep breeds from Khyber Pakhtunkhwa, Pakistan, based on mitochondrial D-loop sequences - Shabir Ahmed; Muhammad Shahid Nadeem; Anna M. Johansson; Elisabeth Jonas; Khushi Muhammad; Sardar Azhar Mehmood (Mammalian Genome, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

Human health risks of heavy metals in water and vegetables: a deterministic and probabilistic study in Gilgit-Baltistan, Pakistan - Nafeesa Khatoon; Sartaj Ali; Azhar Hussain; Jia Huang; Zeyang Li; Zengli Yu; Hongyan Liu (Environmental Geochemistry and Health, 2025)

Continuous forests and non-IBA forest patches provide a safe haven for the tropical bird community in highly fragmented urban landscapes - Sharifah Nur Atikah; Muhammad Syafiq Yahya; Kang Woei Ong; Ruzana Sanusi; Ahmad Razi Norhisham; Badrul Azhar (Biodiversity and Conservation, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

Catalytic insights into laccase for sustainable remediation of multifaceted pharmaceutically active micropollutants from water matrices: A state-of-art review - Imran Ahmad; Saurabh Pal; Mohammad Waseem; Azfar Jamal; Mohammad Azhar Kamal; Fuzail Ahmad; Esraa M. Haji; Sahabjada Siddiqui; Anil Kumar Singh (Journal of Water Process Engineering, 2025)

Grass fields play a greater role in maintaining avian biodiversity in urban landscapes than roadsides - H. M. Bichi; Badrul Azhar; Muhammad Syafiq Yahya; Muhamad Amir Hadi; A. A. Ogunjinmi; Norizah Kamarudin; Ahmad R. Norhisham (Urban Ecosystems, 2025)

Pyocins and Beyond: Exploring the World of Bacteriocins in Pseudomonas aeruginosa - Muhammad Suleman; Allah Rakha Yaseen; Shahbaz Ahmed; Zoha Khan; Asma Irshad; Afsah Pervaiz; Hafiza Hiba Rahman; Muteeba Azhar (Probiotics and Antimicrobial Proteins, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Efficacy of antidiabetic plants available in Himachal Pradesh in management of diabetes: a comprehensive review - Nikita Gupta; Uzma Bano; Neetika Kimta; Azhar Khan; Eugenie Nepovimova; Suliman Y. Alomar; Kamil Kuca (Phytochemistry Reviews, 2025)

Dynamical modeling of Lumpy Skin Disease using Atangana–Baleanu derivative and optimal control analysis - Azhar Iqbal Kashif Butt (Modeling Earth Systems and Environment, 2025)

Nutritional Diagnosis and Morphophysiological Traits of Two Pomegranate Cultivars Under Macronutrient (N, P, K) Deficiencies and Excess - Azhar Ouni; Samia Abboud; Sahar Abdelwahab; Darine Tlili; Soumaya Dbara; Messaoud Mars (Applied Fruit Science, 2025)

Acute toxicity of chloroxylenol detergent on the biology of Musca domestica - Jamila Fatima; Hafiz Azhar Ali Khan; Naeem Iqbal (International Journal of Tropical Insect Science, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Optimizing crowdfunding for mineral resources of Dutch economy: The role of fintech in achieving sustainable development goals through artificial intelligence - Usman Ahmad; Ameenullah Aman; Azam Anwer Khan; Syed Emad Azhar Ali (Resources Policy, 2025)

Synergistic effects of bamboo biochar and ammonia oxidizing bacteria on nitrogen transformation and microbial dynamics during vermicomposting of green waste and chicken manure - Lin Jin; Zeb Azhar; Mengqin Luo; Xiaoqiang Gong (Process Safety and Environmental Protection, 2025)

Similarity of the low-occurrence wind profiles within urban turbulent boundary layers of uniform and non-uniform height block arrays - Muhd Azhar bin Zainol; Wei Wang; Naoki Ikegaya (Building and Environment, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Investigation of a broad diversity of nanoparticles, including their processes, as well as toxicity testing in diverse organs and systems - Azhar U. Khan; Mohammad Qutob; Amel Gacem; Mohd. Rafatullah; Krishna Kumar Yadav; Pankaj Kumar; Javed Khan Bhutto; Meenal Rehman; Sudhakar Bansoid; Lienda Bashier Eltayeb; Nazia Malik; Mohammed Azam Ali; et al. (Toxicology, 2024)

Comparative growth inhibition of 6PPD and 6PPD-Q on microalgae Selenastrum capricornutum, with insights into 6PPD-induced phototoxicity and oxidative stress - Xiaopeng Yan; Claude Kiki; Zijie Xu; Habasi Patrick Manzi; Azhar Rashid; Tianyuan Chen; Qian Sun (Science of The Total Environment, 2024)

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Characterizing mode of inheritance of permethrin resistance in field strains of rice weevil Sitophilus oryzae (Linnaeus) from Pakistan - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal (Journal of Stored Products Research, 2024)

Seasonal and spatial variations in concentration, diversity, and antibiotic resistance of ambient bioaerosols in an arid region - Bilal Sajjad; Azhar Siddique; Kashif Rasool; Khadeeja Abdul Jabbar; Shimaa S. El-Malah; Fares Almomani; M. Rami Alfarra (Environmental Research, 2024)

Assessment of tropospheric NO2 concentrations over greater Doha using Sentinel-5 TROPOspheric monitoring instrument (TROPOMI) satellite data: Temporal analysis, 2018–2023 - Yasir E. Mohieldeen; Shamjad P. Moosakutty; Christos Fountoukis; Azhar Siddique; Mohammed A. Ayoub; M. Rami Alfarra (Environmental Pollution, 2024)

Detection of extended-spectrum beta-lactamase genes among Escherichia coli isolates of buffalo mastitis milk - Sarang Mazhar Abro; Jam Kashif Sahito; Abdul Ahad Soomro; Amjad Hussain Mirani; Muhammad Azhar Memon; Nazeer Hussain Kalhoro (Ecological Genetics and Genomics, 2024)

Impact of fine particulate pollution exposures on respiratory health in a megacity of Pakistan - Qiaoxuan Lin; Ziqiang Lin; Shao Lin; Zafar Fatmi; Nadeem A. Rizvi; Mirza M. Hussain; Azhar Siddique; Omosehin D. Moyebi; David O. Carpenter; Haider A. Khwaja (Atmospheric Pollution Research, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Growth Disturbance, Mineral Nutrient Imbalance, Specific Symptoms and Leaf Characteristics Changes in Two Pomegranate Cultivars Induced by Deficiencies and Excess of Ca, Mg, Zn and Fe - Azhar Ouni; Samia Abboud; Darine Tlili; Sahar Ben Abdelwaheb; Mourad Jellali; Wafaa Bousetta; Messaoud Mars; Soumaya Dbara (Journal of Soil Science and Plant Nutrition, 2024)

Effects of dietary Arthrospira platensis phycocyanin on growth, fatty acid assessment of breast muscles, hematobiochemical, immunological responses, and hepatic histomorphology in broiler chickens - Shimaa A. Amer; Amany Behairy; Amr A. Moustafa; Azhar Eltanahy; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Ahmed Gouda; Simon J. Davies; Samar A. Tolba (Journal of Applied Phycology, 2024)

Comparison of two cultivation methods for domesticating wild red algal eucheumatoids for use in the seaweed industry - Nurulafifah Yahya; Sze-Wan Poong; Juliet Brodie; Elizabeth J. Cottier-Cook; Joanna Wilbraham; Saul Mallinson; Azhar Kassim; Ku Nor Afiza Asnida Ku Mansor; Phaik-Eem Lim (Journal of Applied Phycology, 2024)
Eucheumatoid cultivation is an important alternative livelihood for small-scale farmers in coastal areas in east Malaysia. Over the last 50 years, the same clones of the red eucheumatoid Kappaphycus alvarezii and Kappaphycu s striatus have been vegetatively propagated for cultivation resulting in low genetic diversity. This has made the cultivars more vulnerable to pests and diseases, which has been further exacerbated by climate change. There is an urgent need, therefore, to develop new cultivars that are resilient to pests and diseases, as well as environmental change. In this study, wild eucheumatoids were collected from four regions in Semporna, East Malaysia: Kerindingan, Sibuhun, Sebangkat and Omadal. These eucheumatoids were then grown at a commercial seaweed farm in Silungun, Semporna using two methods: i) tie-tie and ii) basket net for 60 days and their performance was evaluated based on growth and survival rates. A higher mean specific growth rate (SGR) was recorded by wild-collected Kappaphycus spp. (2.15 ± 1.90% day −1 ) and Eucheuma denticulatum (2.83 ± 3.27% day −1 ) when tie-tie was used. However, survival of the wild-collected eucheumatoids was better with the basket net, which led to a reduction in grazing and prevented detachment from culture lines. Of 212 original individuals, 72 survived throughout the study, despite the prevalence of pests and ice-ice disease. Of these, 46.15% Kappaphycus spp. and 50.75% E . denticulatum survived when cultivated using the basket net and 17.20% Kappaphycus spp. and 30.77% E . denticulatum survived when cultivated using tie-tie. The mean SGR and survival rate were significantly correlated with temperature, salinity, pH, current velocity and rainfall (p < 0.05). The surviving wild-collected Kappaphycus spp. and E . denticulatum have the potential to be developed into new cultivars for possible commercial use.

Multiomics approach towards characterization of tumor cell plasticity and its significance in precision and personalized medicine - Mohammad Azhar Aziz (Cancer and Metastasis Reviews, 2024)

First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Predicting permeability in sandstone reservoirs from mercury injection capillary pressure data using advanced machine learning algorithms - Faiq Azhar Abbasi; Areesha Sajjad; Mohsin Ayubi; Ghulam Haider; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney (Arabian Journal of Geosciences, 2024)

Gaseous pollutants linked to pulmonary diseases: East meets West - Fatim Sannoh; Haider A. Khwaja; Zafar Fatmi; Nadeem A. Rizvi; Aftab Turabi; Mirza M. Hussain; Azhar Siddique; David O. Carpenter (Air Quality, Atmosphere & Health, 2024)

Comparative lifespan and healthspan of nonhuman primate species common to biomedical research - Hillary F. Huber; Hannah C. Ainsworth; Ellen E. Quillen; Adam Salmon; Corinna Ross; Adinda D. Azhar; Karen Bales; Michele A. Basso; Kristine Coleman; Ricki Colman; Huda S. Darusman; William Hopkins; et al. (GeroScience, 2024)

Corrigendum to “Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data” [Urban For. Urban Green. 98 (2024) 128415] - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Lead tolerance and accumulation in Arthrocaulon macrostachyum: Growth, physiological and antioxidant responses - Azhar Manzoor; Irfan Aziz; Amtul Mujeeb; Zainul Abideen; Jean Wan Hong Yong (South African Journal of Botany, 2024)

State-of-the-art in ZnS-based nanoarchitects for visible-light photocatalytic degradation of antibiotics and organic dyes - Jamal A. Khan; Shakir Ahamad; Mohd Azhar Hasan Ansari; Mohd Tauqeer; Chae-Hee Park; Jong Pil Park; Chang-Hyung Choi; Akbar Mohammad (Journal of Water Process Engineering, 2024)

Exploring the integrated potential of pyrolysis and low-temperature wet torrefaction for typical medical waste valorization: A multifaceted approach leveraging online TG-FTIR-MS, 2D-COS, iso-conversional kinetics, and reaction mechanisms - Akash Kumar; Lata Kumari; Azhar Ali Laghari; Hongwei Rong; Imtiaz Ali Jamro; Shahdev Sajnani; Moses Akintayo Aborisade; Gulzeb Rajput; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Ghazanfar Mehboob; et al. (Chemical Engineering Journal, 2024)

Resilience underground: Understanding earthworm biomass responses to land use changes in the tropics - Badrul Azhar; Peter van der Meer; Rutger F. Sterenborg; Muhammad Syafiq Yahya; Norhisham Razi; Maisarah Burhanuddin; Jasmijn Rookmaker; Nur Syarihah Sahimi; Welmoed van der Pal; Frisco Nobilly; Siti Aisyah Mohd Azam; Meriam Ubachs; et al. (Biological Conservation, 2024)

Proximal cementation of a collarless polished tapered hip stem: biomechanical analysis using a validated finite element model - Carol Sze Yee Ling; Aiman Izmin; Mitsugu Todo; Azhar M. Merican; Desmond Y. R. Chong (Medical & Biological Engineering & Computing, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

Editing microbes to mitigate enteric methane emissions in livestock - Faheem Ahmed Khan; Azhar Ali; Di Wu; Chunjie Huang; Hamza Zulfiqar; Muhammad Ali; Bilal Ahmed; Muhammad Rizwan Yousaf; Ezi Masdia Putri; Windu Negara; Muhammad Imran; Nuruliarizki Shinta Pandupuspitasari (World Journal of Microbiology and Biotechnology, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Assessing the impact of intervention measures in a mathematical model for monkeypox and COVID-19 co-dynamics in a high-risk population - Andrew Omame; Aeshah A. Raezah; Godwin Amechi Okeke; Tayyaba Akram; Azhar Iqbal (Modeling Earth Systems and Environment, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Integrative approach to mitigate chromium toxicity in soil and enhance antioxidant activities in rice (Oryza sativa L.) using magnesium–iron nanocomposite and Staphylococcus aureus strains - Muhammad Azhar Ali; Muhammad Fahad Sardar; Afzal Ahmed Dar; Mohsin Niaz; Jawad Ali; Qian Wang; Yu Zheng; Yadan Luo; Gadah Albasher; Fengmin Li (Environmental Geochemistry and Health, 2024)

Electroplating sludge derived CuFe2O4/MgFe2O4 metal oxide composites for highly efficient removal of Congo red - Dehui Kong; Jinxiong Wu; Xiuling Yan; Heng Zhang; Azhar Iqbal; Andrei Ivanets; Valentin Romanovski; Lijuan Zhang; Xintai Su (Environmental Science and Pollution Research, 2024)

Biotechnological potentials of surfactants in coal utilization: a review - Nuraly Akimbekov; Ilya Digel; Azhar Zhubanova; Kuanysh T. Tastambek; Atakan Tepecik; Dinara Sherelkhan (Environmental Science and Pollution Research, 2024)
The quest for scientifically advanced and sustainable solutions is driven by growing environmental and economic issues associated with coal mining, processing, and utilization. Consequently, within the coal industry, there is a growing recognition of the potential of microbial applications in fostering innovative technologies. Microbial-based coal solubilization, coal beneficiation, and coal dust suppression are green alternatives to traditional thermochemical and leaching technologies and better meet the need for ecologically sound and economically viable choices. Surfactant-mediated approaches have emerged as powerful tools for modeling, simulation, and optimization of coal-microbial systems and continue to gain prominence in clean coal fuel production, particularly in microbiological co-processing, conversion, and beneficiation. Surfactants (surface-active agents) are amphiphilic compounds that can reduce surface tension and enhance the solubility of hydrophobic molecules. A wide range of surfactant properties can be achieved by either directly influencing microbial growth factors, stimulants, and substrates or indirectly serving as frothers, collectors, and modifiers in the processing and utilization of coal. This review highlights the significant biotechnological potential of surfactants by providing a thorough overview of their involvement in coal biodegradation, bioprocessing, and biobeneficiation, acknowledging their importance as crucial steps in coal consumption.

Pomegranate Peel Extract as 6-Phosphogluconate Dehydrogenase (6PGD) Inhibitor for Treatment of Breast Cancer - Saba Riaz; Azhar Rasul; Matloob Ahmad; Muhammad Asrar; Mudassir Hassan (Cell Biochemistry and Biophysics, 2024)

Methanolic extracts of litchi (Litchi chinensis Sonn.): A novel approach of targeting glucose-6-phosphate dehydrogenase for liver cancer therapy - Lubna Kanwal; Shaukat Ali; Azhar Rasul; Sana Shahbaz; Habiba Anum; Tooba Nauroze (Toxicon, 2024)

Air pollution we breathe: Assessing the air quality and human health impact in a megacity of Southeast Asia - Fatim Sannoh; Zafar Fatmi; David O. Carpenter; Muhayatun Santoso; Azhar Siddique; Kamran Khan; Jahan Zeb; Mirza M. Hussain; Haider A. Khwaja (Science of The Total Environment, 2024)

Control efficacy of isolates of Aspergillus nidulans and Aspergillus fumigatus against three destructive insect pests of stored grain - Hafiz Azhar Ali Khan; Tiyyabah Khan; Naeem Iqbal; Waheed Anwar; Muhammad Ali (Journal of Stored Products Research, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Molecular Phylogenetics of Green-Eyed Skimmers Macromia moorei (Odonata: Corduliidae) of Hazara Region, Pakistan - Sardar Azhar Mehmood; Shabir Ahmed; Ahmed Zia; Wali Khan; Waheed Ali Panhwar (Proceedings of the Zoological Society, 2024)

Correction: Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Diversity, species richness and distribution of grasshoppers (Orthoptera: Acrididae) in Khairpur Sindh Pakistan - Waheed Ali Panhwar; Shabir Ahmed; Sardar Azhar Mehmood; Abdul Manan Shaikh; Wali Khan; Muzafar Shah (International Journal of Tropical Insect Science, 2024)

Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Application of mesenchymal stem cells derived from the umbilical cord or Wharton’s jelly and their extracellular vesicles in the treatment of various diseases - Ayyub Ali Patel; Asma'a H. Mohamed; Jasur Rizaev; Ayaz Khurram Mallick; Maytham T. Qasim; Waleed Al Abdulmonem; Azfar Jamal; Haroonrashid M. Hattiwale; Mohammad Azhar Kamal; Fuzail Ahmad (Tissue and Cell, 2024)

Impact of chitosan/metal oxide-based blends on the rheology, stability, and microstructures of oil-in-water emulsions - Azhar Ayyub; Baoshan Li; Kamran Tahir; Xiao Dong Chen; Shahid Iqbal; Rizwan Ahmed Bhutto; Wajid Rehman; Sana Ullah; Junaid Munawar (Journal of Food Engineering, 2024)

Pathway to environmental sustainability: Assessing the role of productive capacity, remittances, and uncertainty in sub-Saharan Africa - Atif Awad; Mohamed AL Baity; Ilhan Ozturk; M. Azhar Hussain; Abdel Rahman Ahmed Abdel Rahman (Journal of Environmental Management, 2024)

Analyses of groundwater level in a data-scarce region based on assessed precipitation products and machine learning - Ahmed El-Azhari; Ismail Karaoui; Yassine Ait Brahim; Mohamed Azhar; Abdelghani Chehbouni; Lhoussaine Bouchaou (Groundwater for Sustainable Development, 2024)

Maleated Hydroxyethyl Cellulose for the Efficient Removal of Cd(II) Ions from an Aqueous Solution: Isothermal, Kinetic and Regeneration Studies - Fatima Khan; Abu Bakar Siddique; Muhammad Imran Irfan; Muhammad Naeem ul Hassan; Muhammad Sher; Hassan A. Alhazmi; Abdulrahman N. Qramish; Hatem M. A. Amin; Rahman Qadir; Azhar Abbas (Water, Air, & Soil Pollution, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Spatial distribution of physicochemical parameters and drinking and irrigation water quality indices in the Jhelum River - Tofeeq Ahmad; Said Muhammad; Muhammad Umar; Muhammad Usman Azhar; Alaa Ahmed; Ashfaq Ahmad; Rizwan Ullah (Environmental Geochemistry and Health, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Urban heat island phenomenon in a desert, coastal city: The impact of urbanization - J.R. Rajeswari; Christos Fountoukis; Azhar Siddique; Shamjad Moosakutty; Yasir Mohieldeen; Mohammed A. Ayoub; M. Rami Alfarra (Urban Climate, 2024)

Design optimisation of a variable flow CO2 pipeline – A statistical approach - M. Azhar; G.A. Fimbres Weihs; D.E. Wiley (International Journal of Greenhouse Gas Control, 2024)

Site occupancy of native terrestrial mammals in oil palm landscapes is driven by the synergy of land sparing and sharing strategies - Satya Narayana; Amir Affandi; Muhammad Syafiq Yahya; Kamil Azmi Tohiran; Asrulsani Jambari; Ahmad Razi Norhisham; Badrul Azhar (Journal for Nature Conservation, 2024)

No-observed adverse effect levels of deoxynivalenol and aflatoxin B1 in combination induced immune inhibition and apoptosis in vivo and in vitro - Azhar Muhmood; Jiangyu Tang; Jinyan Li; Shuiping Liu; Lili Hou; Guannan Le; Dandan Liu; Kehe Huang (Food and Chemical Toxicology, 2024)

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Assessing bioenergy prospects of algal biomass and yard waste using an integrated hydrothermal carbonization and pyrolysis (HTC–PY): A detailed emission–to–ash characterization via diverse hyphenated analytical techniques and modelling strategies - Akash Kumar; Imtiaz Ali Jamro; Hongwei Rong; Lata Kumari; Azhar Ali Laghari; Baihui Cui; Moses Akintayo Aborisade; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Shahdev Sajnani; Waheed Ali Bhagat; et al. (Chemical Engineering Journal, 2024)

Seroprevalence and contributing factors of transboundary animal diseases in sheep and goats: a study in Peninsular Malaysia - Yonis Ahmed Jimale; Faez Firdaus Abdullah Jesse; Bura Thlama Paul; Eric Lim Teik Chung; Aida Zakaria; Nur Amira Azhar; Mohd Azmi Mohd Lila (Tropical Animal Health and Production, 2024)

Potentiality of Geopora sumneriana against oxidative stress: a case study based on traditional knowledge from India - Roshi Sharma; Sandipta Ghosh; Syed Azhar Jawaid Hashmi; Krishnendu Acharya; Yash Pal Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Correction to: Balancing Ambitions and Realities: Stakeholder Perspectives on Jurisdictional Approach Outcomes in Sabah’s Forests - Julia Su Chen Ng; Colas Chervier; Rachel Carmenta; Zaiton Samdin; Badrul Azhar; Alain Karsenty (Environmental Management, 2024)

Recent Progress of Fluorescent Carbon Dots and Graphene Quantum Dots for Biosensors: Synthesis of Solution Methods and their Medical Applications - Rafaqat Khan; Amina Qureshi; Muhammad Azhar; Zia Ul Hassan; Sagheer Gul; Saeed Ahmad (Journal of Fluorescence, 2024)

Mechanistic approach of tannery wastewater and sulfadiazine mutual toxicity in wheat (Triticum aestivum L.) and mitigation through exogenous application of gallic acid. - Muhammad Nafees; Muhammad Azhar Ali; Linlin Qiu; Ying Yin; Meiling Xu; Guobing Wang; Shafaqat Ali; Hongyan Guo (Chemosphere, 2024)

Multi enzyme production from mixed untreated agricultural residues applied in enzymatic saccharification of lignocellulosic biomass for biofuel - Azhar Ali Tunio; Muhammad Naqvi; Abdul Sattar Qureshi; Imrana Khushk; Abdul Nabi Jatt; Abdul-Sattar Nizami; Habib Ahmed Naqvi; Tanzeel Rehman Charan; Miher Ali Bhutto; Nazir Ahmed Tunio; Qamer-u-Nisa (Process Safety and Environmental Protection, 2024)

Photocatalytic and biological efficacy of Carissa macrocarpa fruit extract-mediated one-pot synthesized ternary metal oxide dual S-scheme heterojunction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Yasir Zaman; Akbar Ali; Muhammad Naeem-ul-Hassan; Javed Iqbal (Journal of Environmental Chemical Engineering, 2024)

Sunlight-assisted green synthesis of gold nanocubes using horsetail leaf extract: A highly selective colorimetric sensor for Pb2+, photocatalytic and antimicrobial agent - Abdul Waheed Khan; Naveed Shahzad Lali; Fahad Y. Sabei; Muhammad Imran Irfan; Muhammad Naeem-ul-Hassan; Muhammad Sher; Awaji Y. Safhi; Abdullah Alsalhi; Ahmed H. Albariqi; Faroq Kamli; Hatem M.A. Amin; Azhar Abbas (Journal of Environmental Chemical Engineering, 2024)

Batch electrocoagulation system for the treatment of Borneo urban river in relation to the industrial zone - Nazeri Abdul Rahman; Calvin Jose Jol; Allene Albania Linus; Siti Noor Linda Taib; Arif Parabi; Wan Wafi Shahanney Wan Borhan; Chieng Kwong Ming; Astisza Syahla Ludmilla Parabi; Nur Syahida Abdul Jalal; Nooranisha Baharuddin; Shaleen Nur Ain Samsul; Nurshazatul’aini Abdul Mutalip; et al. (Journal of Environmental Chemical Engineering, 2024)

Non-thermal pasteurization of milk by elongated electrode moderate electrical field: Chemical and sensory analysis during cold storage and shelf-life determination - Ali Wali M. Alsaedi; Asaad R. Al-Hilphy; Azhar J. Al-Mousawi; Mohsen Gavahian (Innovative Food Science & Emerging Technologies, 2024)

Characterisation of the protein quality and composition of water kefir-fermented casein - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Stan Kubow; Ali Madi Almajwal; Sofyan Maghaydah; Ammar A. Razzak Mahmood; Ali Al-Qaisi; Haya AlFandi (Food Chemistry, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Laboratory assessment of the acaricidal, repellent and anti-cholinesterase effects of Melaleuca alternifolia and Chamaemelum nobile essential oils against Hyalomma scupense ticks - Dhouha Alimi; Najla Trabelsi; Azhar Hajri; Marwa Ben Amor; Asma Mejri; Selim Jallouli; Hichem Sebai (Veterinary Research Communications, 2024)

Repurposing FDA approved drugs against monkeypox virus DNA dependent RNA polymerase: virtual screening, normal mode analysis and molecular dynamics simulation studies - Ahmad Abdul Salam Khan; Muhammad Abrar Yousaf; Jahanzaib Azhar; Muhammad Faisal Maqbool; Ruqia Bibi (VirusDisease, 2024)

Elucidating the genetic diversity and population structure of international cotton germplasm using inter-primer binding site (iPBS) retrotransposon marker system - Binnur Yeşil Bayrıl; Allah Bakhsh; Muhammad Azhar Nadeem; Ufuk Demirel (Genetic Resources and Crop Evolution, 2024)

Tourism triumphs: unraveling the essence of Asia’s allure through governance, FDI, and natural bounties - Muhammad Zaheer Akhtar; Khalid Zaman; Muhammad Azhar Khan (Journal of Environmental Studies and Sciences, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Scenario analysis of local storylines to represent uncertainty in complex human-water systems - Mohammad Reza Alizadeh; Jan Adamowski; Azhar Inam (Journal of Hydrology, 2024)

Unraveling the effect of phenolic extract derived from olive mill solid wastes on agro-physiological and biochemical traits of pomegranate and its associated rhizospheric soil properties - Samia Abboud; Azhar Ouni; Rania Aydi Ben Abdallah; Amani Bchir; Sahar Ben Abdelwaheb; Darine Tlili; Soumaya Dbara (Journal of Hazardous Materials, 2024)

Analysis of population distribution for anticipating radiological consequences of nuclear power plant program in West Kalimantan - Siti Alimah; Euis Etty Alhakim; Ruslan; Sunarko; Yarlina Yacoub; Theo Alvin Ryanto; Akhmad Muktaf Haifani; Yuni Indrawati; Hadi Suntoko; Metasari Kartika; Bintoro Bagus Purmono; Azhar Irwansyah; et al. (Journal of Environmental Radioactivity, 2024)

Non-lamellar lyotropic liquid crystalline nanoparticles as nanocarriers for enhanced drug encapsulation of atorvastatin calcium and proanthocyanidins - Mardhiah Maslizan; Muhammad Salahuddin Haris; Mokrish Ajat; Siti Nurul Ain Md Jamil; Shah Christirani Azhar; N. Idayu Zahid; Intan Diana Mat Azmi (Chemistry and Physics of Lipids, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Calibrated probabilistic sub-seasonal forecasting for Pakistan’s monsoon rainfall in 2022 - Bohar Singh; Muhammad Azhar Ehsan; Andrew W. Robertson (Climate Dynamics, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

Eugenol-Loaded Transethosomal Gel for Improved Skin Delivery and Treatment of Atopic Dermatitis - Bhawna Kashyap; Azhar Khan; Deepak N. Kapoor (AAPS PharmSciTech, 2024)

Superoleophilic cotton fabric decorated with hydrophobic Zn/Zr MOF nanoflowers for efficient self-cleaning, UV-blocking, and oil–water separation - Naseer Ahmad; Sufian Rasheed; Tooba Ali; Irfan Azhar; Waqas Ahmad; Dilshad Hussain (Chemical Engineering Journal, 2024)

Enhanced dye sequestration with natural polysaccharides-based hydrogels: A review - Fiza Majeed; Ammarah Razzaq; Shabnam Rehmat; Irfan Azhar; Abrar Mohyuddin; Nayab Batool Rizvi (Carbohydrate Polymers, 2024)

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Synthesis of coal-biomass blended fuel through coal-wet briquetting technology - Ghulam Haider; Shaine Mohammadali Lalji; Syed Imran Ali; Faiq Azhar Abbasi; Muneeb Burney (Arabian Journal of Geosciences, 2024)

Proteomic analysis of P. gingivalis-Lipopolysaccharide induced neuroinflammation in SH-SY5Y and HMC3 cells - Ambika Verma; Gohar Azhar; Pankaj Patyal; Wei Zhang; Xiaomin Zhang; Jeanne Y. Wei (GeroScience, 2024)

Performance and emission analysis of biodiesel blends enriched with biohydrogen and biogas in internal combustion engines - Osama Khan; Ibrahim Alsaduni; Azhar Equbal; Mohd Parvez; Ashok Kumar Yadav (Process Safety and Environmental Protection, 2024)

Explosion mechanism and volume estimation of volcanic ash during the eruption of Sinabung Volcano on February 19, 2018: Insight from kinematic GPS and seismic data - Estu Kriswati; Irwan Meilano; Mohammad Hasib; Asep Saepuloh; Henri Kuncoro; Bondan Galih Dewanto; Azhar Fuadi (Journal of Volcanology and Geothermal Research, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Metabolisms and multiple functions of laminaran in marine algae under global change: A critical review - Jichen Chen; Azhar Rashid; Shuqi Wang; Xiaojuan Liu; Guang Gao (Carbohydrate Polymers, 2024)

Glucanase Gene of Trichoderma; New Strategy for the Management of Root Rot Disease in Chili - Kiran Nawaz; Waheed Anwar; Muhamamd Nasir Subhani; Adnan Akhter; Sehrish Iftikhar; Hafiz Azhar Ali Khan; Ahmad Ali Shahid (Journal of Soil Science and Plant Nutrition, 2024)

Resistance risk assessment, cross-resistance potential and realized heritability of resistance to methomyl in Musca domestica Linnaeus - Hafiz Azhar Ali Khan (Ecotoxicology, 2024)

The study of genotoxicity and immunotoxicity in workers occupationally exposed to cyanide - Azhar M. Haleem; Nehia N. Hussein (Toxicology and Environmental Health Sciences, 2024)

Optimum quorum quenching bacteria concentration in the better-quality cell entrapping beads to control biofouling in membrane bioreactor - Jennifer Rose; Shinho Chung; Zia Ul Islam; Bushra Azhar; Heekyong Oh (Biofouling, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

Mapping development preferences on the perceived value of ecosystem services and land use conflict and compatibility in Greater Kuala Lumpur - Karen T. Lourdes; Chris N. Gibbins; Ben C. Sherrouse; Darius J. Semmens; Perrine Hamel; Ruzana Sanusi; Badrul Azhar; Jay Diffendorfer; Alex M. Lechner (Urban Forestry & Urban Greening, 2024)

Micro/nanoplastics: Critical review of their impacts on plants, interactions with other contaminants (antibiotics, heavy metals, and polycyclic aromatic hydrocarbons), and management strategies - Ali Raza Khan; Zaid Ulhassan; Guanlin Li; Jiabao Lou; Babar Iqbal; Abdul Salam; Wardah Azhar; Sundas Batool; Tingting Zhao; Kexin Li; Qiuyue Zhang; Xin Zhao; et al. (Science of The Total Environment, 2024)

Modelling terrigenous DOC across the north west European Shelf: Fate of riverine input and impact on air-sea CO2 fluxes - Helen R. Powley; Luca Polimene; Ricardo Torres; Muchamad Al Azhar; Victoria Bell; David Cooper; Jason Holt; Sarah Wakelin; Yuri Artioli (Science of The Total Environment, 2024)

Evaluating the behaviour of axially loaded hollow concrete block masonry walls with small-size openings: Various opening positions and their influence on experimental results - Abrahem A. Ali Blash; B.H. Abu Bakar; Ufuoma Joseph Udi; Azhar Ayad Jaafar; Ilyani Akmar Abu Bakar; Nursyamsi Nursyamsi (Engineering Structures, 2024)

Green fabricated silver nanoparticles as a new eco-friendly insecticide for controlling stored cowpea bug Callosobruchus maculatus (Coleoptera: Bruchidae) - Thirunavukkarasu Santhoshkumar; Rasiravathanahalli Kaveriyappan Govindarajan; Chinnaperumal Kamaraj; Chinnasamy Ragavendran; Mohammad Azhar Kamal; Ehssan H. Moglad; Randa Mohammed Zaki; Arumugam Priyadharsan; Kwang-Hyun Baek (Biocatalysis and Agricultural Biotechnology, 2024)

An experimental study on early age compression and shear strength properties of mixed clay soil - Azhar Abbas; Muhammad Akbar; Pan Huali; Ali Zar; Samar Ramzan; Zahoor Hussain (Arabian Journal of Geosciences, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Recent advances on the therapeutic potential with Ocimum species against COVID-19: A review - Riya Bhattacharya; Debajyoti Bose; Quratulain Maqsood; Khushabu Gulia; Azhar Khan (South African Journal of Botany, 2024)

Effect of temperature on the mechanical properties of fine-grained soils - A review - Md Azhar; Somenath Mondal; Anh Minh Tang; Akhileshwar K. Singh (Geothermics, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Synergistic effect of CuO and Sr doped g-C3N4 for CO2 photoreduction into hydrocarbon fuels - Adil Raza; Azhar Ali Haidry; Zhengjun Yao; Muhammad Farooq Saleem; Asma A. Alothman; Saikh Mohammad (Chemical Engineering Journal, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Balancing Ambitions and Realities: Stakeholder Perspectives on Jurisdictional Approach Outcomes in Sabah’s Forests - Julia Su Chen Ng; Colas Chervier; Rachel Carmenta; Zaiton Samdin; Badrul Azhar; Alain Karsenty (Environmental Management, 2024)

Experimental study on the purification capacity of potted plants on low-concentration carbon monoxide in indoor environment - Jintuo Zhu; Jinyu Liu; Xinjian He; Liang Wang; Xuejing Liu; Jin Yang; Haisong Sun; Noor Azhar; Nkansah Benjamin Oduro (Environmental Science and Pollution Research, 2023)

Spatiotemporal profile and ecological impacts of major and trace elements in surface sediments of marginal seas of the Arctic and Northern Pacific Oceans - Azhar Rashid; Chao Fang; Dan Qin; Yusheng Zhang; François Nkinahamira; Jun Bo; Qian Sun (Marine Pollution Bulletin, 2023)

Antioxidant, anti-inflammatory, and anti-apoptotic effects of genkwanin against aflatoxin B1-induced testicular toxicity - Muhammad Umar Ijaz; Ayesha Ishtiaq; Arfa Tahir; Mughees Aizaz Alvi; Azhar Rafique; Peng Wang; Guo-ping Zhu (Toxicology and Applied Pharmacology, 2023)

Characterizing the HMA gene family in dragon fruit (Selenicereus undatus L.) and revealing their response to multifactorial stress combinations and melatonin-mediated tolerance - Qamar U Zaman; Latif Ullah Khan; Muhammad Azhar Hussain; Asif Ali; Liu Hui; Aamir Ali Khokhar; Darya Khan; Hua-Feng Wang (South African Journal of Botany, 2023)

Efficacy of entomopathogenic fungi against three major stored insect pests, Rhyzopertha dominica, Sitophilus zeamais and Trogoderma granarium - Hafiz Azhar Ali Khan; Tiyyabah Khan (Journal of Stored Products Research, 2023)

Development of a behaviour pattern-based testing approach for coupled socioeconomic and environmental models - Mohammad Reza Alizadeh; Xingyu Peng; Jan Adamowski; Raffaele Albano; Bogdan Ozga-Zielinski; Azhar Inam (Journal of Environmental Management, 2023)

Forecast skill of Bangladesh summer monsoon rainfall in C3S and NMME models after calibration - Muhammad Azhar Ehsan; Bohar Singh (Dynamics of Atmospheres and Oceans, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Redox state of the Dharwar craton root as inferred from eclogite and peridotite sourced mantle cargo, with implications for kimberlite and lamproite magma formation - Azhar M. Shaikh; Yannick Bussweiler; Fanus Viljoen; Robert Bolhar; S. Ravi; Dominik C. Hezel; Henriëtte Ueckermann; Sebastian Tappe (Contributions to Mineralogy and Petrology, 2023)

Hydrogeochemical facies analysis of groundwater at parts of south-western Bangladesh: a case study - M. Moklesur Rahman; Azhar Mahmud; Md. Al Amin; Md. Shahadat Hossain; Ling Bai; Molla Rahman Shaibur; Md. Aliur Rahman; Abu Shamim Khan (Arabian Journal of Geosciences, 2023)

Feasibility assessment of self-deicing concrete pavements with recycled CFRP reinforcement: Environmental and mechanical performance - Abdullah Al Moman; Ali Azhar Butt; Somayeh Nassiri (Resources, Conservation and Recycling, 2023)

Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal Sajjad; Kashif Rasool; Azhar Siddique; Khadeeja Abdul Jabbar; Shimaa S. El-Malaha; Muhammad Umar Sohail; Fares Almomani; M. Rami Alfarra (Environmental Pollution, 2023)

Probing the Förster Resonance Energy Transfer Dynamics in Colloidal Donor-Acceptor Quantum Dots Assemblies - Muhammad Adnan Khalid; Muhammad Mubeen; Maria Mukhtar; Zumaira Siddique; Poshmal Sumreen; Firdevs Aydın; Demet Asil; Azhar Iqbal (Journal of Fluorescence, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Therapeutic Potential of Selenium Nanoparticles on Letrozole-Induced Polycystic Ovarian Syndrome in Female Wistar Rats - Maisra Azhar Butt; Hafiz Muhammad Shafique; Mahjabeen Mustafa; Nurain Baig Moghul; Anum Munir; Urwah Shamas; Sobia Tabassum; Mubin Mustafa Kiyani (Biological Trace Element Research, 2023)

Efficacy of zinc-based nanoparticles in alleviating the abiotic stress in plants: current knowledge and future perspectives - Ali Raza Khan; Wardah Azhar; Xingming Fan; Zaid Ulhassan; Abdul Salam; Muhammad Ashraf; Yihua Liu; Yinbo Gan (Environmental Science and Pollution Research, 2023)

Overview of fermentation process: structure-function relationship on protein quality and non-nutritive compounds of plant-based proteins and carbohydrates - Mohammad Alrosan; Thuan-Chew Tan; Wee Yin Koh; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu’datt (Critical Reviews in Food Science and Nutrition, 2023)

Effect of sub-lethal and lethal concentrations of the entomopathogenic fungus Metarhizium anisopliae Sorokin on detoxification enzymes and demographic parameters of Mythimna separata (Walker) - Momina Azhar; Shoaib Freed; Hira Sabir; Samina Rafique; Afifa Naeem; Rizwan Ahmed (Crop Protection, 2023)

Genotype responsive growth performance and salinity tolerance of tilapia hybrid (Oreochromis niloticus × O. mossambicus) - Bhakta Supratim Sarker; Md. Shamim Reza Sabuz; Md. Golam Azom; Nusrat Easmin; Azhar Ali; Md. Samsul Alam; M. Sadiqul Islam (Aquaculture, 2023)

Pistacia lentiscus essential oil and its pure active components as acaricides to control Dermanyssus gallinae (Acari: Mesostigmata) - Dhouha Alimi; Azhar Hajri; Selim Jallouli; Hichem Sebai (Veterinary Parasitology, 2023)

Towards sustainable and selective detection of lead Ions: Selaginella bryopteris assisted green synthesis of gold nanoparticles with tunable properties - Afsar H. Rizvi; Mohd. Azhar Aziz; Alim H. Naqvi; Absar Ahmad (Journal of Environmental Chemical Engineering, 2023)

Conservation planning in national parks may benefit from site occupancy and detection estimates of native animal species - Asrulsani Jambari; Tetsuro Hosaka; Miyabi Nakabayashi; Muhammad Syafiq Yahya; Badrul Azhar (Journal for Nature Conservation, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Pro-inflammatory cytokines and reproductive hormone responses in bucks post-challenge with Mannheimia haemolytica A2 and its outer membrane protein - Nur Amira Azhar; Bura Thlama Paul; Faez Firdaus Abdullah Jesse; Mohd-Azmi Mohd-Lila; Eric Lim Teik Chung; Mat Isa Kamarulrizal (Tropical Animal Health and Production, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

How various stakeholder pressure influences mega-project sustainable performance through corporate social responsibility and green competitive advantage - Azhar Ali; Li Ma; Mohsin Shahzad; Jonathan Musonda; Shahid Hussain (Environmental Science and Pollution Research, 2023)

Literature review on pavements and electric vehicle interaction: A research roadmap - Thomas Mattinzioli; Ali Azhar Butt; John Harvey (Transportation Research Part D: Transport and Environment, 2023)

Effect of temperature and relative humidity on the efficacy of spinetoram against Sitophilus granarius, Sitophilus zeamais and Tribolium castaneum - Hafiz Azhar Ali Khan (Journal of Stored Products Research, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

Urbanization influenced the interactions between dissolved organic matter and bacterial communities in rivers - Binessi Edouard Ifon; Bob Adyari; Liyuan Hou; Okugbe Ebiotubo Ohore; Azhar Rashid; Chang-Ping Yu; Hu Anyi (Journal of Environmental Management, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Expression variations of DNA damage response genes ATM and ATR in blood cancer patients - Aamir Parvez; Ishrat Mahjabeen; Azhar Mehmood; Asad Ullah Khan; Asif Nisar; Mahmood Akhtar Kayani (Molecular Genetics and Genomics, 2023)

Recent advances in chromosome capture techniques unraveling 3D genome architecture in germ cells, health, and disease - Nuruliarizki Shinta Pandupuspitasari; Faheem Ahmed Khan; Chunjie Huang; Azhar Ali; Muhammad Rizwan Yousaf; Farwa Shakeel; Ezi Masdia Putri; Windu Negara; Anis Muktiani; Bambang Waluyo Hadi Eko Prasetiyono; Limbang Kustiawan; Dimar Sari Wahyuni (Functional & Integrative Genomics, 2023)

Investigation of lateral cyclic load capacity of screw pile group in multi clay layer - Hassan Obaid Abbas; Azhar Subhi Ibrahim (Arabian Journal of Geosciences, 2023)

Assessment of long-term trends in chlorophyll-a and sea surface temperature in the Arabian Sea and their association with aerosols using remote sensing - Yunpeng Sun; Pengpeng Gao; Salman Tariq; Ayesha Azhar; Zia ul Haq; Usman Mehmood (Ocean & Coastal Management, 2023)

Identifying indicator bird species for sustainable oil palm plantation certification - Zulkifli Nursyamin; Muhammad Syafiq Yahya; Sharifah Nur Atikah; Kamil Azmi Tohiran; Ahmad R. Norhisham; Nurul Wahida Othman; Alex M. Lechner; Badrul Azhar (Journal of Cleaner Production, 2023)

Non-thermal pasteurization of milk by an innovative energy-saving moderate electrical field equipped with elongated electrodes and process optimization - Ali Wali M. Alsaedi; Azhar J. Al-Mousawi; Asaad R. Al-Hilphy; Mohsen Gavahian (Innovative Food Science & Emerging Technologies, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Examining the microbial composition of natural springs in Bhaderwah, Jammu and Kashmir, India - Abhishek Gupta; Vandana Dutt; Neeraj Sharma; Swapnil Kajale; Arun Bhatt; Shuja Shafi; Esam Azhar; Alimuddin Zumla; Avinash Sharma (Environmental Monitoring and Assessment, 2023)

Multi-species rotational grazing of small ruminants regenerates undergrowth vegetation while controlling weeds in the oil palm silvopastoral system - Kamil Azmi Tohiran; Frisco Nobilly; Raja Zulkifli; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Md Zainal Rasyidi; Badrul Azhar (Agricultural Systems, 2023)

Do silvopastoral management practices affect biological pest control in oil palm plantations? - Frisco Nobilly; Sharifah Nur Atikah; Muhammad Syafiq Yahya; Shokri Jusoh; Thomas M. R. Maxwell; Ahmad Razi Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Badrul Azhar (BioControl, 2023)

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Continuous electrocoagulation treatment system for partial desalination of tropical brackish peat water in Sarawak coastal peatlands - Nazeri Abdul Rahman; Calvin Jose Jol; Allene Albania Linus; Wan Wafi Shahanney Wan Borhan; Nur Syahida Abdul Jalal; Nooranisha Baharudin; Shaleen Nur Ain Samsul; Nurshazatul'aini Abdul Mutalip; Airul Azhar Jitai; Dayang Fadhilatul Aisyah Abang Abdul Hamid (Science of The Total Environment, 2023)

Hematological, immuno-antioxidant disruptions, and genes down-regulation induced by Aeromonas veronii challenge in Clarias gariepinus: The ameliorative role of silica nanoparticles - Afaf N. Abdel Rahman; Hassnaa Mahmoud Elsheshtawy; Engy Mohamed Mohamed Yassin; Ahmed Omran; Marwa Abo Hashem; Azhar Eltanahy; Tarek Khamis; Sameh H. Ismail; Morteza Yousefi; Heba H. Mahboub (Fish & Shellfish Immunology, 2023)

Exogenous application of low and high molecular weight organic acids differentially affected the uptake of cadmium in wheat-rice cropping system in alkaline calcareous soil - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Muhammad Azhar; Muhammad Rizwan; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Zahoor Ahmad (Environmental Pollution, 2023)

Cyclic loading effect on batter anchored pile group in dry sand - Ali H. Ahmed; Hassan O. Abbas; Azhar S. Ibrahim (Geotechnical and Geological Engineering, 2023)

Toxicity, resistance and metabolic mechanism of resistance to permethrin in larvae of laboratory and field strains of Musca domestica L. - Hafiz Azhar Ali Khan; Sumaira Maqsood; Anas Mahmood (Journal of Asia-Pacific Entomology, 2023)

Extraction of dietary fiber and polyphenols from mango peel and its therapeutic potential to improve gut health - Amna Tariq; Amna Sahar; Muhammad Usman; Aysha Sameen; Marriam Azhar; Rimsha Tahir; Rimsha Younas; Muhammad Issa Khan (Food Bioscience, 2023)

Transmission mechanisms of antibiotic resistance genes in arsenic-contaminated soil under sulfamethoxazole stress - Zhuoqing Li; Xinqi Wang; Beibei Zhang; Bingyu Li; Huihui Du; Zhibin Wu; Azhar Rashid; Caleb Oppong Mensah; Ming Lei (Environmental Pollution, 2023)

A systematic literature review on public participation in decision-making for local authority planning: A decade of progress and challenges - Azlan Abas; Kadir Arifin; Mohd Azhar Mohamed Ali; Muhammad Khairil (Environmental Development, 2023)

Flexible and Photo-responsive superwetting surfaces based on porous materials coated with Mussel-Inspired Azo-Copolymer - Jian Chen; Xu Chen; Umair Azhar; Xiaoyu Yang; Chunhua Zhou; Mei Yan; Hui Li; Chuanyong Zong (Chemical Engineering Journal, 2023)

Reforestation could bring native mammal species back in the tropical highlands - Siti Wahdaniyah; Ku Noor Khalidah; Nabilah Hamidah Sabar; Norizah Kamarudin; Ruzana Sanusi; Norhisham Ahmad Razi; Alex M. Lechner; Badrul Azhar (Tropical Ecology, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Elucidating the genetic variations among Turkish grape varieties using morphological and molecular markers - Ahmet Sümbül; Ercan Yildiz; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2023)

The application of chemometrics in metals source of identification in Brunei Bay surface sediment. - Meng Chuan Ong; Jaw Chuen Yong; Hasrizal Shaari; Bidai Joseph; Noor Azhar Mohamed Shazili; Siriporn Pradit; Ghazali Adiana (Environmental Geochemistry and Health, 2023)

Conservation strategy, phytochemical diversity, and genetic consistency assessment of in vitro propagated perennial herb Vincetoxicum hirundinaria Medik - Ajmal Khan; Azhar Hussain Shah; Niaz Ali; Abdul Majid; Saad Hussain Shah (In Vitro Cellular & Developmental Biology - Plant, 2023)

Outbreak simulation of Litopenaeus vannamei recovery rate with oral alginate and spirulina diet supplementation against Vibrio parahaemolyticus AHPND - Nuril Azhar; Ervia Yudiati (Aquaculture International, 2023)

Application of KHSO5 for remediation of soils polluted by organochlorides: A comprehensive study on the treatment's efficacy, environmental implications, and phytotoxicity - Belay Tafa Oba; Xuehao Zheng; Moses Akintayo Aborisade; Akash Kumar; Ashenafi Yohannes Battamo; Jiashu Liu; Azhar Ali Laghari; Peizhe Sun; Yongkui Yang; Lin Zhao (Science of The Total Environment, 2023)

Mode of inheritance of field-evolved resistance to pirimiphos-methyl in Sitophilus oryzae (Linnaeus) (Coleoptera: Curculionidae) - Hafiz Azhar Ali Khan; Tiyyabah Khan (Journal of Stored Products Research, 2023)

Microbial Diversity of Soils Contaminated with Persistent Organic Pollutants and POP-Degrading Strains - Azhar Malik; Gulzhamal Abdieva; Perizat Ualieva (Water, Air, & Soil Pollution, 2023)

Potential of green-synthesized ZnO NPs against human ovarian teratocarcinoma: an in vitro study - Mohd Shahnawaz Khan; Nojood Altwaijry; Nasimudeen R. Jabir; Abdulaziz Mohammed Alamri; Mohammad Tarique; Azhar U. Khan (Molecular Biology Reports, 2023)

Smallholder oil palm plantation sustainability assessment using multi-criteria analysis and unmanned aerial vehicles - Yong Bin Wong; Chris Gibbins; Badrul Azhar; Su Shen Phan; Paul Scholefield; Reza Azmi; Alex M. Lechner (Environmental Monitoring and Assessment, 2023)
Oil palm agriculture has caused extensive land cover and land use changes that have adversely affected tropical landscapes and ecosystems. However, monitoring and assessment of oil palm plantation areas to support sustainable management is costly and labour-intensive. This study used an unmanned aerial vehicles (UAV) to map smallholder farms and applied multi-criteria analysis to data generated from orthomosaics, to provide a set of sustainability indicators for the farms. Images were acquired from a UAV, with structure from motion (SfM) photogrammetry then used to produce orthomosaics and digital elevation models of the farm areas. Some of the inherent problems using high spatial resolution imagery for land cover classification were overcome by using texture analysis and geographic object-based image analysis (OBIA). Six spatially explicit environmental metrics were developed using multi-criteria analysis and used to generate sustainability indicator layers from the UAV data. The SfM and OBIA approach provided an accurate, high-resolution (~5 cm) image-based reconstruction of smallholder farm landscapes, with an overall classification accuracy of 89%. The multi-criteria analysis highlighted areas with lower sustainability values, which should be considered targets for adoption of sustainable management practices. The results of this work suggest that UAVs are a cost-effective tool for sustainability assessments of oil palm plantations, but there remains the need to plan surveys and image processing workflows carefully. Future work can build on our proposed approach, including the use of additional and/or alternative indicators developed through consultation with the oil palm industry stakeholders, to support certification schemes such as the Roundtable on Sustainable Palm Oil (RSPO).

The mechanism linking the variability of the Antarctic sea ice extent in the Indian Ocean sector to Indian summer monsoon rainfall - Siti Syairah Atiqah Azhar; Sheeba Nettukandy Chenoli; Azizan Abu Samah; Seong-Joong Kim; Nuncio Murukesh (Climate Dynamics, 2023)

Potential of agroforestry orchards as a conservation set-aside initiative in industrial rubber tree and oil palm plantations for avian biodiversity - Muhammad Syafiq Yahya; Sharifah Nur Atikah; Izereen Mukri; Aslinda Oon; Ainil Hawa; Ruzana Sanusi; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (Biodiversity and Conservation, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Fine particulate matter and its chemical constituents' levels: A troubling environmental and human health situation in Karachi, Pakistan - Omosehin D. Moyebi; Zafar Fatmi; David O. Carpenter; Muhayatun Santoso; Azhar Siddique; Kamran Khan; Jahan Zeb; Mirza M. Hussain; Haider A. Khwaja (Science of The Total Environment, 2023)

Enhanced textile dye removal from wastewater using natural biosorbent and Shewanella algae B29: Application of Box Behnken design and genomic approach - Kamel Chaieb; Bochra Kouidhi; Lamia Ayed; Salman Bakr Hosawi; Jawaher Abdulbaqi Abdulhakim; Azhar Hajri; Hisham N. Altayb (Bioresource Technology, 2023)

Synthesis and Characterizations of Graphene/Copper Ferrite for Efficient Arsenic Removal - M. Abdullah; G. Murtaza; Muhammad Azhar Khan (Water, Air, & Soil Pollution, 2023)

Polycyclic Aromatic Hydrocarbon (PAH)–Contaminated Soil Decontamination Through Vermiremediation - Samrendra Singh Thakur; Azhar Rashid Lone; Kiran Singh; Siddhartha Shankar Bhattacharyya; Anisa Ratnasari; Ajar Nath Yadav; Subodh Kumar Jain; Shweta Yadav (Water, Air, & Soil Pollution, 2023)

Understanding the quality and potential of groundwater for human purposes and peat fire disaster mitigation - Nur Islami; Mitri Irianti; Azhar Azhar; Muhammad Nor; Fakhruddin Fakhruddin (Arabian Journal of Geosciences, 2023)

Poultry manure gleaned antibiotic residues in soil environment: A perspective of spatial variability and influencing factors - Azhar Rashid; Juma Muhammad; Sardar Khan; Aatika Kanwal; Qian Sun (Chemosphere, 2023)

A comprehensive review on water pollution, South Asia Region: Pakistan - Rabeea Noor; Aarish Maqsood; Azhar Baig; Chaitanya B. Pande; Syeda Mishal Zahra; Abu Saad; Mariyam Anwar; Sudhir Kumar Singh (Urban Climate, 2023)

Evaluation of quality and protein structure of natural water kefir-fermented quinoa protein concentrates - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt; Ghada Mohamed Aleid; Mohammad N. Alhamad; Sofyan Maghaydah (Food Chemistry, 2023)

Biodiversity of Insects Parasitoid and Predator in Cassava Agroecosystem in Indonesia - Ihsan Nurkomar; Dina Wahyu Trisnawati; Azru Azhar; Jefri Ardi Saputra; Aswinda Damar Prayoga (Proceedings of the Zoological Society, 2023)

Agroforestry orchards support greater butterfly diversity than monoculture plantations in the tropics - Wan Mamat Wan Zaki; Muhammad Syafiq Yahya; Ahmad R. Norhisham; Ruzana Sanusi; Peter J. van der Meer; Badrul Azhar (Oecologia, 2023)

Sensitivity analysis of moment magnitude (Mw) spectral fitting parameters based on orthogonal design: using aftershocks of the 2019 Mw 6.5 Ambon, Indonesia earthquake - Dian Kusumawati; David P. Sahara; Andri D. Nugraha; Nanang T. Puspito; Sri Widiyantoro; Zulfakriza Zulfakriza; Shindy Rosalia; Hasbi Ash Shiddiqi; Ardianto Ardianto; Aria Widhi Baskara; Andi Azhar Rusdin; Adi Wibowo; et al. (Bulletin of Earthquake Engineering, 2023)

Hydrocarbon seepage detection by integrating remotely sensed and geochemical data: scanning the lithological alteration - Namam M. Salih; Rayan Gh. Thannoun; Azhar Kh. Bety (Arabian Journal of Geosciences, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Correction to: Differential plasma protein expression after ingestion of essential amino acid-based dietary supplement versus whey protein in low physical functioning older adults - Gohar Azhar; Ambika Verma; Xiaomin Zhang; Amanda Pangle; Pankaj Patyal; Wei Zhang; Yingni Che; Karen Coker; Robert R. Wolfe; Jeanne Y. Wei (GeroScience, 2023)

Drinking water quality assessment based on index values incorporating WHO guidelines and Bangladesh standards - M. Moklesur Rahman; Tasfimul Haque; Azhar Mahmud; Md Al Amin; Md Sahadat Hossain; Md Yeasir Hasan; Molla Rahman Shaibur; Sabbir Hossain; Md Alamgir Hossain; Ling Bai (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

MSR influence on environmental & ecological balance: Mediating effect of environmental regulations & strategies - Li Ma; Jonathan Musonda; Azhar Ali (Journal of Cleaner Production, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

Pyrolysis of de-fatted microalgae residue: A study on thermal-kinetics, products’ optimization, and neural network modelling - Akash Kumar; Imtiaz Ali Jamro; Beibei Yan; Zhanjun Cheng; Junyu Tao; Shengquan Zhou; Lata Kumari; Jian Li; Moses Akintayo Aborisade; Belay Tafa Oba; Waheed Ali Bhagat; Azhar Ali Laghari; et al. (Fuel, 2023)

Lipopolysaccharide aggravates canine influenza a (H3N2) virus infection and lung damage via mTOR/autophagy in vivo and in vitro - Mengmeng Wang; Haolei Li; Shuiping Liu; Lei Ge; Azhar Muhmood; Dandan Liu; Fang Gan; Yunhuan Liu; Xingxiang Chen; Kehe Huang (Food and Chemical Toxicology, 2023)

Development of methods for the simplification of complex group built causal loop diagrams: A case study of the Rechna doab - Muhammad Asif; Azhar Inam; Jan Adamowski; Muhammad Shoaib; Hisham Tariq; Shakil Ahmad; Mohammad Reza Alizadeh; Aftab Nazeer (Ecological Modelling, 2023)

Bacillus Species as Direct-Fed Microbial Antibiotic Alternatives for Monogastric Production - Shifa A. Bahaddad; Meshal H. K. Almalki; Othman A. Alghamdi; Sayed S. Sohrab; Muhammad Yasir; Esam I. Azhar; Hichem Chouayekh (Probiotics and Antimicrobial Proteins, 2023)

Differential plasma protein expression after ingestion of essential amino acid-based dietary supplement verses whey protein in low physical functioning older adults - Gohar Azhar; Ambika Verma; Xiaomin Zhang; Amanda Pangle; Pankaj Patyal; Wei Zhang; Yingni Che; Karen Coker; Robert R. Wolfe; Jeanne Y. Wei (GeroScience, 2023)
In a recent randomized, double-blind, placebo-controlled trial, we were able to demonstrate the superiority of a dietary supplement composed of essential amino acids (EAAs) over whey protein, in older adults with low physical function. In this paper, we describe the comparative plasma protein expression in the same subject groups of EAAs vs whey. The plasma proteomics data was generated using SOMA scan assay. A total of twenty proteins were found to be differentially expressed in both groups with a 1.5-fold change. Notably, five proteins showed a significantly higher fold change expression in the EAA group which included adenylate kinase isoenzyme 1, casein kinase II 2-alpha, Nascent polypeptide-associated complex subunit alpha, peroxiredoxin-1, and peroxiredoxin-6. These five proteins might have played a significant role in providing energy for the improved cardiac and muscle strength of older adults with LPF. On the other hand, fifteen proteins showed slightly lower fold change expression in the EAA group. Some of these 15 proteins regulate metabolism and were found to be associated with inflammation or other comorbidities. Gene Ontology (GO) enrichment analysis showed the association of these proteins with several biological processes. Furthermore, protein–protein interaction network analysis also showed distinct networks between upregulated and downregulated proteins. In conclusion, the important biological roles of the upregulated proteins plus better physical function of participants in the EAAs vs whey group demonstrated that EAAs have the potential to improve muscle strength and physical function in older adults. This study was registered with ClinicalTrials.gov: NCT03424265 “Nutritional interventions in heart failure.”

State of gaseous air pollutants and resulting health effects in Karachi, Pakistan - Omosehin D. Moyebi; Fatim Sannoh; Zafar Fatmi; Azhar Siddique; Kamran Khan; Jahan Zeb; Mirza M. Hussain; David O. Carpenter; Haider A. Khwaja (Environmental Monitoring and Assessment, 2023)

A Review and Perspective of Environmental Disinfection Technology Based on Microwave Irradiation - Liming Liu; Na Wang; Azhar Ali Laghari; Hong Li; Can Wang; Zhenyu Zhao; Xin Gao; Qiang Zeng (Current Pollution Reports, 2023)

Climate-induced optimal wheat cropping season and mapping districts vulnerabilities in Punjab, Pakistan - Azhar Ali Janjua; Muhammad Aslam (Environment, Development and Sustainability, 2023)

The Combined Effect of Beetroot Peel Extract, Chilling, and Vacuum Packaging on the Shelf-Life of Deccan Mahseer ( Tor khudree ) Steaks - Hafsa Maqbool; Zynudheen Abubacker; Muhammad P. Safeena; Mudassir Azhar; C.G. Joshy (Journal of Aquatic Food Product Technology, 2023)

Insight into variation and controlling factors of dissolved organic matter between urban rivers undergoing different anthropogenic influences - Binessi Edouard Ifon; Bob Adyari; Liyuan Hou; Lanping Zhang; Xin Liao; Philomina Onyedikachi Peter; Azhar Rashid; Chang-Ping Yu; Anyi Hu (Journal of Environmental Management, 2023)

Melatonin-mediated resistance to copper oxide nanoparticles-induced toxicity by regulating the photosynthetic apparatus, cellular damages and antioxidant defense system in maize seedlings - Ali Raza Khan; Xingming Fan; Abdul Salam; Wardah Azhar; Zaid Ulhassan; Jiaxuan Qi; Fiza Liaquat; Shuaiqi Yang; Yinbo Gan (Environmental Pollution, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Assessing the genetic diversity in hawthorn (Crataegus spp.) genotypes using morphological, phytochemical and molecular markers - Ercan Yildiz; Ahmet Sümbül; Mehmet Yaman; Muhammad Azhar Nadeem; Ahmet Say; Faheem Shehzad Baloch; Gheorghe Cristian Popescu (Genetic Resources and Crop Evolution, 2023)

Evaluation of operational and financial viability models of combined landfill site for intermediate cities in Pakistan - Abdullah Yasar; Salman Basit; Amt-ul Bari Tabinda; Azhar Ali; Syeda Um-e-Kalsoom Naqvi; Abdul-Sattar Nizami; Syeda Laiba Haider Naqvi; Shakeel Mahmood; Rameesha Tanveer (Environmental Science and Pollution Research, 2023)

The influence of compost amendments on bioaccumulation of potentially toxic elements by pea plant cultivated in mine degraded soils - Abdulnour Ali Jazem Ghanim; Muhammad Azhar Shah; Mehboob Alam; Anwarzeb Khan; Muhammad Amjad Khan; Saifur Rahman; Mabkhoot A. Alsaiari; Mohammed Jalalah; Mohammad Kamal Asif Khan; Muhammad Irfan; Zawar Hussain (Arabian Journal of Geosciences, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Taxonomy and distribution of butterfly fauna of family pieridae (lepidoptera) in district abbottabad, Khyber Pakhtunkhwa, Pakistan - Sidra Taj; Shoaib Ali; Shabir Ahmed; Muhammad Ather Rafi; Sardar Azhar Mehmood; Muzafar Shah (International Journal of Tropical Insect Science, 2022)

Evaluation of Potential Predictability of Indian Summer Monsoon Rainfall in ECMWF's Fifth-Generation Seasonal Forecast System (SEAS5) - Raju Attada; Muhammad Azhar Ehsan; Prasanth A. Pillai (Pure and Applied Geophysics, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Dirty versus clean fuel for cooking in Pakistan: regional mapping and correlates - Tusawar Iftikhar Ahmad; Muhammad Atif Nawaz; Kokab Kiran; Vishal Dagar; Muhammad Azhar Bhatti; Altaf Hussain (Environmental Science and Pollution Research, 2022)

Ethylene accelerates copper oxide nanoparticle-induced toxicity at physiological, biochemical, and ultrastructural levels in rice seedlings - Wardah Azhar; Ali Raza Khan; Abdul Salam; Zaid Ulhassan; Jiaxuan Qi; Gulmeena shah; Yihua Liu; Yang Chunyan; Shuaiqi Yang; Yinbo Gan (Environmental Science and Pollution Research, 2022)

Biopesticides and insect pest management - Kanwal Hanif; Muhammad Zubair; Dilbar Hussain; Sikander Ali; Muhammad Saleem; Hafiz Azhar Ali Khan; Tamsila Nazir; Muhammad Waqas ul Hassan (International Journal of Tropical Insect Science, 2022)

Fyn and Lyn gene polymorphisms impact the risk of thyroid cancer - Asif Nisar; Mahmood Akhtar Kayani; Wajiha Nasir; Azhar Mehmood; Malik Waqar Ahmed; Aamir Parvez; Ishrat Mahjabeen (Molecular Genetics and Genomics, 2022)

Application of HEC-HMS for Hydrological Modeling of Upper Sabarmati River Basin, Gujarat, India - Rekha Verma; Mohammed Sharif; Azhar Husain (Modeling Earth Systems and Environment, 2022)

Influence of COVID-19 on the sustainability of livestock performance and welfare on a global scale - Md. Tanvir Rahman; Md. Saiful Islam; Awad A. Shehata; Shereen Basiouni; Hafez M. Hafez; Esam I. Azhar; Asmaa F. Khafaga; Fulvia Bovera; Youssef A. Attia (Tropical Animal Health and Production, 2022)

Seminal and histopathological alterations in bucks challenged with Mannheimia haemolytica serotype a2 and its LPS endotoxin - Nur Amira Azhar; Bura Thlama Paul; Faez Firdaus Abdullah Jesse; Eric Lim Teik Chung; Mat Isa Kamarulrizal; Mohd Azmi Mohd Lila (Tropical Animal Health and Production, 2022)

Genetic differentiation in wild Kappaphycus Doty and Eucheuma J. Agardh (Solieriaceae, Rhodophyta) from East Malaysia reveals high inter- and intraspecific diversity with strong biogeographic signal - Ji Tan; Pui-Ling Tan; Sze-Wan Poong; Janina Brakel; Claire Gachon; Juliet Brodie; Ahemad Sade; Azhar Kassim; Phaik-Eem Lim (Journal of Applied Phycology, 2022)

Pathogenic role of cytokines in COVID-19, its association with contributing co-morbidities and possible therapeutic regimens - Ayesha Tanveer; Bushra Akhtar; Ali Sharif; Uzma Saleem; Azhar Rasul; Aftab Ahmad; Kashif Jilani (Inflammopharmacology, 2022)

Correction to: The impact of COVID‑19 on the sustainability of the environment, animal health and food security, and safety - Ibrahim H. Alshubaith; Salah Alhajri; Ahlam Alhajri; Raed A. Alsultan; Esam I. Azhar; Bakr Hussain Alhussaini; Lafi S. Al Solami; Maria Cristina de Oliveira; Asmaa F. Khafaga; Adel D. Alqurashi; Youssef A. Attia (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: The impact of COVID-19 on the sustainability of the environment, animal health and food security, and safety - Ibrahim H. Alshubaith; Salah Alhajri; Ahlam Alhajri; Raed A. Alsultan; Esam I. Azhar; Bakr Hussain Alhussaini; Lafi S. Al Solami; Maria Cristina de Oliveira; Asmaa F. Khafaga; Adel D. Alqurashi; Youssef A. Attia (Environmental Science and Pollution Research, 2022)

Metagenomic Insights into the Gut Microbiota of Eudrilus eugeniae (Kinberg) and Its Potential Roles in Agroecosystem - Samrendra Singh Thakur; Azhar Rashid Lone; Sailu Yellaboina; Subodh Tambat; Ajar Nath Yadav; Subodh Kumar Jain; Shweta Yadav (Current Microbiology, 2022)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Tetra-primers ARMS-PCR Based Association Analyses of Synonymous and Intronic Variants in the ADAM12 Gene with Susceptibility to Knee Osteoarthritis: A Case-Control Study - Sehrish Fatima; Bushra Khan; Obaid Yusuf Khan; Maryam Amjad; Sitwat Zehra; Abid Azhar (Biochemical Genetics, 2022)

Correction to: First report of Rickettsia asembonensis in small ruminants - Van Lun Low; Siti Sarah Azhar; Tiong Kai Tan; Premaalatha Bathmanaban; Sazaly AbuBakar; Panchadcharam Chandrawathani; Hassan Nizam Quaza Nizamuddin; Mohd Saeid Faizah Hanim; Ngah Hamid Akma; Mohd Noor Norlizan; Yvonne Ai Lian Lim (Veterinary Research Communications, 2022)

First report of Rickettsia asembonensis in small ruminants - Van Lun Low; Siti Sarah Azhar; Tiong Kai Tan; Premaalatha Bathmanaban; Sazaly AbuBakar; Panchadcharam Chandrawathani; Hassan Nizam Quaza Nizamuddin; Mohd Saeid Faizah Hanim; Ngah Hamid Akma; Mohd Noor Norlizan; Yvonne Ai Lian Lim (Veterinary Research Communications, 2022)

Morphological and molecular characterization of Auricularia villosula from India - Uzma Altaf; Syed Azhar Jawad Hashmi; Yash Pal Sharma (Indian Phytopathology, 2022)

Molecular pathogenesis of Japanese encephalitis and possible therapeutic strategies - Sanjay Kumar; Akanksha Verma; Pardeep Yadav; Sumit Kumar Dubey; Esam Ibraheem Azhar; S. S. Maitra; Vivek Dhar Dwivedi (Archives of Virology, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Recent progress in omics and biotechnological approaches for improved mango cultivars in Pakistan - Ghassan Zahid; Yıldız Aka Kaçar; Flavien Shimira; Sara Iftikhar; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2022)

2-Methoxyestradiol inhibits carotid artery intimal hyperplasia induced by balloon injury via inhibiting JAK/STAT axis in rats - Ahmad S. Azhar; Ashraf B. Abdel-Naim; Osama M. Ashour (Environmental Science and Pollution Research, 2022)

In Vivo Effects of Orally Administered Different Concentrations of Silver Oxide Nanoparticles in Hyperuricemic Mice - Mubin Mustafa Kiyani; Nurain Baig Moghul; Ambreen Javed; Maisra Azhar Butt; Hassan Burair Abbas; Hamza Rehman; Tausif Ahmed Rajput; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Changes in selected cytokines, acute-phase proteins, gonadal hormones and reproductive organs of non-pregnant does challenged with Mannheimia haemolytica serotype A2 and its LPS endotoxin - Mat Isa Kamarulrizal; Eric Lim Teik Chung; Faez Firdaus Abdullah Jesse; Bura Thlama Paul; Amira Nur Azhar; Mohd Azmi Mohd Lila; Annas Salleh; Yusuf Abba; Mohd Shafarin Shamsuddin (Tropical Animal Health and Production, 2022)

Morphological and molecular characterization of Pluteus species (Pluteaceae) from India - Uzma Altaf; Komal Verma; Syed Azhar Jawad Hashmi; Yash Pal Sharma (Indian Phytopathology, 2022)

New insights into host-pathogen interactions in papaya dieback disease caused by Erwinia mallotivora in Carica papaya - Muniroh Md Saad; Rabiatul-Adawiah Zainal-Abidin; Mohd Azhar Hassan; Norliza Abu Bakar (European Journal of Plant Pathology, 2022)

Analyzing the role of meteorological parameters and CO2 emissions towards crop production: empirical evidence from South Asian countries - Zia Ul-Haq; Usman Mehmood; Salman Tariq; Fazzal Qayyum; Ayesha Azhar; Hasan Nawaz (Environmental Science and Pollution Research, 2022)

Mapping the Delivery of Ecological Functions Combining Field Collected Data and Unmanned Aerial Vehicles (UAVs) - Stefano Schenone; Mihailo Azhar; César Adrián Victoria Ramírez; Alfonso Gastelum Strozzi; Patrice Delmas; Simon F. Thrush (Ecosystems, 2022)

Viruses as tools in gene therapy, vaccine development, and cancer treatment - Musab bin Umair; Fujimura Nao Akusa; Hadia Kashif; Seerat-e-Fatima; Fatima Butt; Marium Azhar; Iqra Munir; Muhammad Ahmed; Wajeeha Khalil; Hafiz Sharyar; Shazia Rafique; Muhammad Shahid; et al. (Archives of Virology, 2022)

Molecular forces governing protein-protein interaction: Structure-function relationship of complexes protein in the food industry - Mohammad Alrosan; Thuan-Chew Tan; Azhar Mat Easa; Sana Gammoh; Muhammad H. Alu'datt (Critical Reviews in Food Science and Nutrition, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Stabilization of expansive soil subgrade by waste plastic - Mantu Kumar; Mohammad Azhar; Somenath Mondal; Rakesh Pratap Singh (Arabian Journal of Geosciences, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

The role of selected odonate nymphs in biological control of Culex quinquefasciatus larvae, and effect of glyphosate herbicide on their predatory performance - Sami Ullah Khan; Sardar Azhar Mehmood; Hazrat Ali; Waqas Waqas; Bakht Rahbar (International Journal of Tropical Insect Science, 2022)

Anti-Hyperuricemic Effect of Iron Oxide Nanoparticles against Monosodium Urate Crystals Induced Gouty Arthritis in BALB/c Mice - Mubin Mustafa Kiyani; Nurain Baig Moghul; Maisra Azhar Butt; Hamza Rehman; Ramsha Masood; Tausif Ahmed Rajput; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Narcotic detection efficacy and behavior of police dogs are affected by rearing system, weaning time, and maternal bond - Azhar F. Abdel Fattah; Enas N. Said; Mayada R. Farag (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Comparison of effectiveness of introduced barn owls, Tyto javanica javanica, and rodenticide treatments on rat control in oil palm plantations - Cik Mohd Rizuan Zainal Abidin; Hafidzi Mohd Noor; Noor Hisham Hamid; Shakinah Ravindran; Chong Leong Puan; Azhar Kasim; Hasber Salim (Journal of Pest Science, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Arabiibacter massiliensis gen. nov. sp. nov., New Anaerobic Bacterium Isolated from the Human Gut - Cheikh Ibrahima Lo; Sory Ibrahima Traore; Awa Diop; Melhem Bilen; Esam Ibraheem Azhar; Fehmida Bibi; Asif Jiman-Fatani; Muhammad Yasir; Jean-Christophe Lagier; Didier Raoult; Florence Fenollar; Pierre-Edouard Fournier (Current Microbiology, 2022)

Synergistic evaluation of Moringa oleifera extract and ß-lactam antibiotic to restore the susceptibility of methicillin-resistant Staphylococcus aureus - Soma Vankwani; Asma Ansari; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2022)

Nonlinearity in the relationship between COVID-19 cases and carbon damages: controlling financial development, green energy, and R&D expenditures for shared prosperity - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Hailan Salamun; Sasmoko; Yasinta Indrianti; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2022)

Evaluation of Antioxidant Activity and Histopathological Changes Occurred by the Oral Ingestion of CuO Nanoparticles in Monosodium Urate Crystal-Induced Hyperuricemic BALB/c Mice - Mubin Mustafa Kiyani; Maisra Azhar Butt; Hamza Rehman; Moheen Mustafa; Abdul Ghafoor Sajjad; Syed Sajid Hussain Shah; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2022)

Evaluating the experimental cultivation of edible mushroom, Volvariella volvacea underneath tree canopy in tropical agroforestry systems - Nurul Kamaliah; Sabiha Salim; Sumaiyah Abdullah; Frisco Nobilly; Sapari Mat; Ahmad R. Norhisham; Kamil Azmi Tohiran; Raja Zulkifli; Alex M. Lechner; Badrul Azhar (Agroforestry Systems, 2022)

Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Azhar Rasul; Mirza Muhammad Faran Ashraf Baig (Natural Product Research, 2021)

Two new anticancer phenolic derivatives from leaves of Piper betle Linn. - Akhtar Atiya; Mohammed Azhar Salim; Barij Nayan Sinha; Uma Ranjan Lal (Natural Product Research, 2021)

DNA barcoding and genetic variability of earthworms (Clitellata: Oligochaeta) with new records from Mizoram, India - Azhar Rashid Lone; Samrendra Singh Thakur; Nalini Tiwari; Olusola B. Sokefun; Shweta Yadav (Organisms Diversity & Evolution, 2021)

Anticonvulsant activity of methanolic extract of Withania cogulans in mice - Zenat Fatima Khattak; Bushra Ansari; Muhammad Jamal; Abdul Aleem Awan; Muhammad Azhar Sherkheli; Rizwan ul Haq (Metabolic Brain Disease, 2021)

A review on efficient electromagnetic interference shielding materials by recycling waste—a trio of land to lab to land concept - Sarika Verma; Medha Mili; Manish Dhangar; Krishnasamy Jagatheesan; Sriparna Paul; Harsh Bajpai; Nimisha Vedanti; Jyotirmoy Mallik; Mohammed Akram Khan; Hari Narayan Bhargaw; Sayed Azhar Rasheed Hashmi; Avanish Kumar Srivastava (Environmental Science and Pollution Research, 2021)

The impact of coal combustion, nitrous oxide emissions, and traffic emissions on COVID-19 cases: a Markov-switching approach - Muhammad Khalid Anser; Danish Iqbal Godil; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro (Environmental Science and Pollution Research, 2021)

The mediating role of ICTs in the relationship between international tourism and environmental degradation: fit as a fiddle - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Seasonal predictability of Ethiopian Kiremt rainfall and forecast skill of ECMWF's SEAS5 model - Muhammad Azhar Ehsan; Michael K. Tippett; Andrew W. Robertson; Mansour Almazroui; Muhammad Ismail; Tufa Dinku; Nachiketa Acharya; Asher Siebert; Jemal Seid Ahmed; Asaminew Teshome (Climate Dynamics, 2021)

Virulence attitude estimation of Pasteurella multocida isolates in embryonated chicken eggs - Azhar G. Shalaby; Neveen R. Bakry; Azza S. El-Demerdash (Archives of Microbiology, 2021)

Rainfall forecasting in upper Indus basin using various artificial intelligence techniques - Muhammad Hammad; Muhammad Shoaib; Hamza Salahudin; Muhammad Azhar Inam Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah (Stochastic Environmental Research and Risk Assessment, 2021)

Optimizing the Design of Blood–Brain Barrier-Penetrating Polymer-Lipid-Hybrid Nanoparticles for Delivering Anticancer Drugs to Glioblastoma - Taksim Ahmed; Fuh-Ching Franky Liu; Chungsheng He; Azhar Z. Abbasi; Ping Cai; Andrew M. Rauth; Jeffery T. Henderson; Xiao Yu Wu (Pharmaceutical Research, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

First report of Lasiodiplodia theobromae as causal agent of strawberry dieback in Punjab, Pakistan - Nasir Mehmood; Abid Riaz; Imran Hassan; Salman Ghuffar; Abdul Sattar; Wajid Aurangzeb; Sohaib Azhar (Journal of Plant Pathology, 2021)

Financial development, oil resources, and environmental degradation in pandemic recession: to go down in flames - Muhammad Khalid Anser; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Does COVID-19 pandemic disrupt sustainable supply chain process? Covering some new global facts - Muhammad Khalid Anser; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Deciphering the genetic diversity and population structure of Turkish bread wheat germplasm using iPBS-retrotransposons markers - Muhammad Azhar Nadeem (Molecular Biology Reports, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Antifouling paint biocides (Irgarol 1051 and diuron) in the selected ports of Peninsular Malaysia: occurrence, seasonal variation, and ecological risk assessment - Hassan Rashid Ali; Marinah Mohd Ariffin; Tuan Fauzan Tuan Omar; Adiana Ghazali; Mohammed Ali Sheikh; Noor Azhar Mohamed Shazili; Zainudin Bachok (Environmental Science and Pollution Research, 2021)

Air pollution and hospitalization in megacities: empirical evidence from Pakistan - Usman Mehmood; Ayesha Azhar; Fazzal Qayyum; Hasan Nawaz; Salman Tariq; Zia ul Haq (Environmental Science and Pollution Research, 2021)

Reproductive traits, behavioral and hormonal changes during breeding season in Egyptian Geese under natural photoperiod - Azhar F. Abdel Fattah; Noura E. Abd Elhameed; Elshimaa M. Roushdy; Mohamed S. El Kholy; Mahmoud Alagawany (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Exploring the genetic diversity and population structure of scarlet eggplant germplasm from Rwanda through iPBS-retrotransposon markers - Flavien Shimira; Hatice Filiz Boyaci; Yeter Çilesiz; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Hatıra Taşkin (Molecular Biology Reports, 2021)

Causal relationship between mafic magma underplating and migmatization of arc crust: Evidence from the Madras block of Southern Granulite terrane, India - Mohd Azhar Ul Haq; S Balakrishnan; Rajneesh Bhutani; Jitendra K Dash (Journal of Earth System Science, 2021)

Clostridium culturomicium sp. nov. and Clostridium jeddahitimonense sp. nov., novel members of the Clostridium genus isolated from the stool of an obese Saudi Arabian - Hoang Thong Kieu; Noémie Garrigou; Amael Fadlane; Ludivine Brechard; Nicholas Armstrong; Philippe Decloquement; Muhammad Yasir; Esam Ibraheem Azhar; Saad B. Al-Masaudi; Jean-Christophe Lagier; Maryam Tidjani Alou; Didier Raoult (Current Microbiology, 2021)

Association of genetic polymorphism rs2071676 in carbonic anhydrase gene (CA9) with the risk of squamous cell carcinoma of lungs and esophagus - Saima Saleem; Ramsha Khan; Ghulam Haider; Sara Hasan; Faria Fatima; Sitwat Zehra; Abid Azhar (Biologia, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

Efficacy of rhizobacterial exopolysaccharides in improving plant growth, physiology, and soil properties - Abubakar Dar; Zahir Ahmad Zahir; Muhammad Iqbal; Atif Mehmood; Atif Javed; Azhar Hussain; Bushra; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2021)

Origins of olivine in Earth’s youngest kimberlite: Igwisi Hills volcanoes, Tanzania craton - Azhar M. Shaikh; Sebastian Tappe; Yannick Bussweiler; Christian Vollmer; Richard J. Brown (Contributions to Mineralogy and Petrology, 2021)

Genetic dissection of days to flowering via genome-wide association studies in Turkish common bean germplasm - Muhammad Azhar Nadeem; Ephrem Habyarimana; Tolga Karaköy; Faheem Shehzad Baloch (Physiology and Molecular Biology of Plants, 2021)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

Progress in nuclear energy with carbon pricing to achieve environmental sustainability agenda: on the edge of one’s seat - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Sameh E. Askar; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Regional mapping of climate variability index and identifying socio-economic factors influencing farmer’s perception in Bangladesh - Sifat E. Rabbi; Reza Shant; Sourav Karmakar; Azhar Habib; Jürgen P. Kropp (Environment, Development and Sustainability, 2021)

Demographic, psychological, and environmental factors affecting student’s health during the COVID-19 pandemic: on the rocks - Muhammad Khalid Anser; Muhammad Sharif; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Khalid Zaman; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Responses of testosterone hormone and important inflammatory cytokines in bucks after challenge with Mannheimia haemolytica A2 and its LPS endotoxin - Nur Amira Azhar; Bura Thlama Paul; Faez Firdaus Abdullah Jesse; Eric Lim Teik Chung; Kamarulrizal Mat Isa; Mohd Azmi Mohd Lila; Abd Wahid Haron (Tropical Animal Health and Production, 2021)

Genome-wide association and transcriptome analysis of root color-related genes in Gossypium arboreum L. - Zibo Zhao; Daowu Hu; Muhammad Tehseen Azhar; Hongge Li; Chenhui Ma; Shoupu He; Xiaoyang Wang; Gaofei Sun; Tahir Mahmood; Washu Dev; Xiongming Du (Planta, 2021)

The role of information and communication technologies in mitigating carbon emissions: evidence from panel quantile regression - Muhammad Khalid Anser; Munir Ahmad; Muhammad Azhar Khan; Khalid Zaman; Abdelmohsen A. Nassani; Sameh E. Askar; Muhammad Moinuddin Qazi Abro; Ahmad Kabbani (Environmental Science and Pollution Research, 2021)

Pyriproxyfen induces lethal and sublethal effects on biological traits and demographic growth parameters in Musca domestica - Hafiz Azhar Ali Khan (Ecotoxicology, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Pyrethroid exposure: as determinant of CYP1A1 and GSTP1 genetic variations in occupationally exposed Sindh farmers - Iffat Imran; Saima Saleem; Abid Azhar; Sitwat Zehra (Biologia, 2021)

Chemical characterization and anti-arthritic appraisal of Monotheca buxifolia methanolic extract in Complete Freund’s Adjuvant-induced arthritis in Wistar rats - Muhammad Furqan Akhtar; Khushdil Khan; Ammara Saleem; Mirza Muhammad Faran Ashraf Baig; Azhar Rasul; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Dietary Lactobacillus plantarum Relieves Nile Tilapia (Oreochromis niloticus) Juvenile From Oxidative Stress, Immunosuppression, and Inflammation Induced by Deltamethrin and Aeromonas hydrophila - Mahmoud S. Gewaily; Mustafa Shukry; Marwa F. Abdel-Kader; Mohamed Alkafafy; Foad A. Farrag; Eman M. Moustafa; Hien Van Doan; Mohamed F. Abd-Elghany; Ahmed F. Abdelhamid; Azhar Eltanahy; Mahmoud A. O. Dawood (Frontiers in Marine Science, 2021)
Aeromonas hydrophila infection is one of the major diseases that cause inflammation and immunodepression in aquatic animals. Likewise, waterborne toxins are known for their negative impact on the immunity and antioxidant responses of aquatic organisms. In this study, Lactobacillus plantarum (LP20) was incorporated in Nile tilapia, Oreochromis niloticus , diets (50 mg/kg) to investigate its role in the antioxidant capacity, immunity, and anti-inflammation induced by deltamethrin (DLM) toxicity (96-h LC 50 was 14.9 μg/L) and A. hydrophila (LD 50 , 2 × 10 8 CFU/ml). One hundred and twenty healthy fish with an initial weight of 28.21 ± 1.34 g were allotted in 12 glass aquaria (60 L) and divided randomly into four groups (triplicates, 10 fish per aquarium). The control fish neither received LP20 nor were exposed to DLM. The second group of fish was fed the control diet and subjected to DLM (DLM group). The third group of fish was provided with LP20 without DLM toxicity (LP20 group), and the fourth group of fish was fed LP20 and subjected to DLM (DLM + LP20 group). After 30 days, fish were intraperitoneally injected with A. hydrophila . Ten days post infection, the survival rate was lower in fish exposed to DLM than those exposed to LP20. Further, fish fed on LP20 had elevated serum total protein (sTP), albumin (ALB), globulin (GLB), phagocytic index (PI), phagocytic (PA), and lysozyme activities (LZM), but they had lower urea, uric acid bilirubin, creatinine, glucose, aspartate aminotransferase (AST), alkaline phosphatase (ALP), and alanine aminotransferase (ALT) activities after 24 h, 48 h, and 1 week post A. hydrophila challenge. However, fish exposed to DLM had lower sTP, ALB, GLB and higher urea, uric acid, bilirubin, creatinine, glucose, ALT, AST, and ALP after 24 h, 48 h, and 1 week post A. hydrophila challenge. Markedly, after the A. hydrophila challenge, fish exposed to DLM + LP20 displayed upregulated levels of superoxide dismutase ( SOD ), catalase ( CAT ), and glutathione peroxidase ( GPx ) genes. The transcription of interferon gamma ( IFN- γ), interleukin 12 ( IL-12 ), and tumor necrosis factor alpha ( TNF- α) was upregulated in DLM and DLM + LP20 groups. Fish exposed to DLM downregulated interleukin 8 ( IL-8 ) gene expression after A. hydrophila challenge. Further, fish displayed upregulation of heat shock protein 70 ( HSP70 ) gene expression after DLM toxicity. Besides, fish exposed to DLM toxicity and A. hydrophila infection had severe inflammatory features in the liver, spleen, gills, and intestine, while dietary LP20 relieved the inflammatory features. In summary, dietary LP20 relieves Nile tilapia from oxidative stress, immunosuppression, and inflammation induced by DLM and A. hydrophila infection.

Disintegration of uncertainties associated with real-time multi-satellite precipitation products in diverse topographic and climatic area in Pakistan - Muhammad Masood; Ghulam Nabi; Muhammad Babur; Aftab Hussain Azhar; Muhammad Kaleem Ullah (Journal of Mountain Science, 2021)

Multi-stage magmatic history of olivine–leucite lamproite dykes from Banganapalle, Dharwar craton, India: evidence from compositional zoning of spinel - Satya P. Kumar; Azhar M. Shaikh; Suresh C. Patel; Janisar M. Sheikh; Duryadhan Behera; Kamal L. Pruseth; Subramanian Ravi; Sebastian Tappe (Mineralogy and Petrology, 2021)

Integrated use of phosphate-solubilizing Bacillus subtilis strain IA6 and zinc-solubilizing Bacillus sp. strain IA16: a promising approach for improving cotton growth - Iqra Ahmad; Maqshoof Ahmad; Azhar Hussain; Moazzam Jamil (Folia Microbiologica, 2021)

Enhancement of Zinc Ion Removal from Water by Physically Mixed Particles of Iron/Iron Sulfide - Yuya Kamba; Miharu Ueta; Md. Azhar Uddin; Yoshiei Kato (Water, Air, & Soil Pollution, 2021)

Diversity and recombination analysis of Cotton leaf curl Multan betasatellite associated with cotton leaf curl begomovirus disease complex - Muhammad Zubair; Saleem Ur Rahman; Ishtiaq Hassan; Azhar Hussain Shah; Imran Amin; Shahid Mansoor (Australasian Plant Pathology, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Sedimentological attributes of the Middle Jurassic peloids-dominated carbonates of eastern Tethys, lesser Himalayas, Pakistan - Abdus Saboor; Muhammad Haneef; Muhammad Hanif; Muhammad Azhar Farooq Swati (Carbonates and Evaporites, 2020)

The Effect of Tropical Cyclone Nicholas (11–20 February 2008) on Sea Level Anomalies in Indonesian Waters - Nining Sari Ningsih; Farrah Hanifah; Tika Sekar Tanjung; Laela Fitri Yani; Muchamad Al Azhar (Journal of Marine Science and Engineering, 2020)
As reported extensively in both electronic and print media in Indonesia, high wave and anomalously high sea level phenomena occurred in February 2008 in Indonesian waters, mainly along the western coast of Sumatra and the southern coasts of Java-Bali. Tropical Cyclone (TC) Nicholas, occurring in northwestern coastal waters of Australia between 11 and 20 February 2008, might have contributed to the existence of these phenomena in the Indonesian region. This study focused on investigating the effect of TC Nicholas on the increases in sea levels in the Indonesian waters by analyzing residual water levels (non-astronomic tide). In this regard, a storm tide event (the sum of the astronomical tide and storm surge generated by the TC Nicholas) was simulated in this region using the Regional Ocean Modeling System (ROMS). The residual water levels were obtained by removing the tidal part (astronomic tide) from the ROMS simulated total water levels. In addition, to confirm possible influences of TC Nicholas, a lagged correlation analysis was applied between atmospheric pressure at the center of TC Nicholas and residual water level oscillations in the Indonesian waters. It was found that the residual water levels showed a strong correlation with the atmospheric pressure at the center of TC Nicholas in some areas of the Indonesian seas, such as the western coast of Sumatra, the southern coast of Java, Lesser Sunda Islands, and the southern coast of Papua. The increased sea levels on the western coast of Sumatra are up to 16 cm, with TC Nicholas leading the residual water level by 4.18 days (TL: time lag). Meanwhile, they are up to 20 cm (TL = 5.75 days), 21 cm (TL = 1.12 days), and 38 cm (TL = 3.96 days) on the southern coast of Java, the Lesser Sunda Islands, and the southern coast of Papua, respectively. The results of this study could be used as an initial assessment to investigate the most vulnerable Indonesian coastal areas to the impact of the TC and they might be significantly beneficial for designing both a proper disaster risk reduction program and investment policies in the region, particularly in the context of flood risk reduction and adaptation.

Predicting peak summer monsoon precipitation over Pakistan in ECMWF SEAS5 and North American Multimodel Ensemble - Muhammad Azhar Ehsan; Michael K. Tippett; Fred Kucharski; Mansour Almazroui; Muhammad Ismail (International Journal of Climatology, 2020)
The potential and actual forecast skill of peak summer monsoon precipitation (July–August [JA]) over the core summer monsoon region of Pakistan (CSMRP: 68°–76°E, 30°–36°N) is investigated. The predictions from the latest version of the European Centre for Medium‐Range Weather Forecast System5 (SEAS5) and the North American Multimodel Ensemble (NMME) initialized in the beginning of June, May, and April are utilized. The potential skill is estimated by signal‐to‐noise ratio and perfect model correlation. The forecast skill is evaluated using the temporal anomaly correlation as well as the ranked probability skill score for probabilistic forecasts. The SEAS5 generally captures the observed climatological mean and variability patterns of peak summer monsoon precipitation over the region, with some biases mainly located over the complex topography zones. Observed SST anomalies in the El Niño–Southern Oscillation (ENSO) region are negatively correlated with observed peak summer monsoon precipitation over the region. The ENSO–precipitation connection is weakly reproduced in SEAS5 at Lead‐1 and fades gradually with increasing lead time. The potentially predictable component (signal) is small compared to the unpredictable part (noise). Nonetheless, statistically significant potential skill is found over the CSMRP. However, the forecast skill of peak summer monsoon precipitation over the region is lower than the potential skill in SEAS5. A multimodel ensemble average of five models shows little benefit in predicting peak monsoon precipitation over Pakistan. Extended spatial averaging has some impact on the skill; however, temporal averaging has no effect on the skill of the summer monsoon precipitation in SEAS5. Together these results show limitations of the current seasonal prediction models and demonstrate their inadequate performance in predicting peak summer monsoon precipitation over Pakistan.

Evaluating the relationship between climate variability and agricultural crops under indeterminacy - Azhar Ali Janjua; Muhammad Aslam; Naheed Sultana (Theoretical and Applied Climatology, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

Exopolysaccharides and indole-3-acetic acid producing Bacillus safensis strain FN13 potential candidate for phytostabilization of heavy metals - Farheen Nazli; Moazzam Jamil; Azhar Hussain; Tanveer Hussain (Environmental Monitoring and Assessment, 2020)

Assessment of Real Time, Multi-Satellite Precipitation Products under Diverse Climatic and Topographic Conditions - Muhammad Masood; Abdul Sattar Shakir; Aftab Hussain Azhar; Guhlam Nabi; Habib-u-Rehman (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Social and administrative issues related to the COVID-19 pandemic in Pakistan: better late than never - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Xuan Hinh Vo; Khalid Zaman (Environmental Science and Pollution Research, 2020)

Application of geoelectrical resistivity method for the assessment of shallow aquifer quality in landfill areas - Nur Islami; Mitri Irianti; Fakhruddin Fakhruddin; Azhar Azhar; Muhammad Nor (Environmental Monitoring and Assessment, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

The impacts of COVID-19 measures on global environment and fertility rate: double coincidence - Muhammad Khalid Anser; Zahid Yousaf; Muhammad Azhar Khan; Xuan Hinh Voo; Abdelmohsen A. Nassani; Saad M. Alotaibi; Muhammad Moinuddin Qazi Abro; Khalid Zaman (Air Quality, Atmosphere & Health, 2020)

Heat Activated Zeolite for the Reduction of Ammoniacal Nitrogen, Colour, and COD in Landfill Leachate - Hamidi Abdul Aziz; Ahmad Fauzi Mohd Noor; Yap Wei Keat; Motasem Y. D. Alazaiza; Azhar Abd Hamid (International Journal of Environmental Research, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

RNA isolation efficacy of commercial and modified conventional methods for Citrus tristeza virus and mRNA internal control amplification - Nesheman Huma; Shagufta Sahar; Yasir Iftikhar; Abid Azhar; Saddia Galani (Biologia, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Examining the impacts of future land use/land cover changes on climate in Punjab province, Pakistan: implications for environmental sustainability and economic growth - Abdus Samie; Azhar Abbas; Muhammad Masood Azeem; Sidra Hamid; Muhammad Amjed Iqbal; Shaikh Shamim Hasan; Xiangzheng Deng (Environmental Science and Pollution Research, 2020)

Biofloc-based co-culture systems of Nile tilapia (Oreochromis niloticus) and redclaw crayfish (Cherax quadricarinatus) with different carbon–nitrogen ratios - Muhammad H. Azhar; Suciyono Suciyono; Darmawan S. Budi; Mohammad F. Ulkhaq; Mai Anugrahwati; Julie Ekasari (Aquaculture International, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

Activation of death receptor, DR5 and mitochondria-mediated apoptosis by a 3,4,5-trimethoxybenzyloxy derivative in wild-type and p53 mutant colorectal cancer cell lines - Zachariah Chee Ken Chan; Kok Hoong Leong; Huda Salah Kareem; Anwar Norazit; Suzita Mohd Noor; Azhar Ariffin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Colorectal cancer in Saudi Arabia as the proof-of-principle model for implementing strategies of predictive, preventive, and personalized medicine in healthcare - Mesnad Alyabsi; Abdulrahman Alhumaid; Haafiz Allah-Bakhsh; Mohammed Alkelya; Mohammad Azhar Aziz (EPMA Journal, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Potential predictability of boreal winter precipitation over central-southwest Asia in the North American multi-model ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui (Climate Dynamics, 2020)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Influence of biochar amendment and foliar application of iron oxide nanoparticles on growth, photosynthesis, and cadmium accumulation in rice biomass - Muhammad Rizwan; Shamaila Noureen; Shafaqat Ali; Sarwat Anwar; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Azhar Hussain (Journal of Soils and Sediments, 2019)

Discriminating between large-scale oil palm plantations and smallholdings on tropical peatlands using vegetation indices and supervised classification of LANDSAT-8 - Aslinda Oon; Helmi Zulhaidi Mohd Shafri; Alex Mark Lechner; Badrul Azhar (International Journal of Remote Sensing, 2019)

Time-dependent impairments in learning and memory in Streptozotocin-induced hyperglycemic rats - Ayaz Ahmed; Guirong Zeng; Dejiang Jiang; Haiying Lin; Mudassar Azhar; Ahsana Dar Farooq; Muhammad Iqbal Choudhary; Xinmin Liu; Qiong Wang (Metabolic Brain Disease, 2019)

Potential predictability of Arabian peninsula summer surface air temperature in the North American multimodel ensemble - Muhammad Azhar Ehsan; Fred Kucharski; Mansour Almazroui; Muhammad Ismail; Michael K. Tippett (Climate Dynamics, 2019)

Geochemistry and sediment in the main stream of the Ca River basin, Vietnam: weathering process, solute-discharge relationships, and reservoir impact - Ho Thi Phuong; Kenji Okubo; Md. Azhar Uddin (Acta Geochimica, 2019)

Vulnerability, well-being, and livelihood adaptation under changing environmental conditions: a case from mountainous region of Pakistan - Laila Shahzad; Arifa Tahir; Faiza Sharif; Waqas Ud Din Khan; Muhammad Ansar Farooq; Azhar Abbas; Zulfiqar Ahmad Saqib (Environmental Science and Pollution Research, 2019)

Cytotoxic Effects of Titanium Dioxide Nanaoparticles Synthesized by Laser Technique on Peripheral Blood Lymphocytes and Hep-2 Cell Line - Azhar M. Haleem; Ruaa H. Abbas; Mohammed Abed Jawad; Faiz Alberaqdar (Toxicology and Environmental Health Sciences, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Association analysis and allelic distribution of deletion in CC chemokine receptor 5 gene (CCR5Δ32) among breast cancer patients of Pakistan - Faria Fatima; Saima Saleem; Abdul Hameed; Ghulam Haider; Syed Aqib Ali Zaidi; Madiha Kanwal; Sitwat Zehra; Abid Azhar (Molecular Biology Reports, 2019)

Role of biochar and plant growth promoting rhizobacteria to enhance soil carbon sequestration—a review - Rubab Sarfraz; Azhar Hussain; Asma Sabir; Ibtissem Ben Fekih; Allah Ditta; Shihe Xing (Environmental Monitoring and Assessment, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Role of viruses, prions and miRNA in neurodegenerative disorders and dementia - Sayed Sartaj Sohrab; Mohd Suhail; Ashraf Ali; Mohammad Amjad Kamal; Azamal Husen; Fahim Ahmad; Esam Ibraheem Azhar; Nigel H. Greig (VirusDisease, 2018)

The P3 kimberlite and P4 lamproite, Wajrakarur kimberlite field, India: mineralogy, and major and minor element compositions of olivines as records of their phenocrystic vs xenocrystic origin - Azhar M. Shaikh; Satya P. Kumar; Suresh C. Patel; Satyajeet S. Thakur; Subramanian Ravi; Duryadhan Behera (Mineralogy and Petrology, 2018)

Effects of 1-Methylcyclopropene on Rice Growth Characteristics and Superior and Inferior Spikelet Development Under Salt Stress - Sajid Hussain; Chu Zhong; Zhigang Bai; Xiaochuang Cao; Lianfeng Zhu; Azhar Hussain; Chunquan Zhu; Shah Fahad; Allen Bohr James; Junhua Zhang; Qianyu Jin (Journal of Plant Growth Regulation, 2018)

Bioremediation of tannery effluent by Cr- and salt-tolerant bacterial strains - Sobia Ashraf; Muhammad Naveed; Muhammad Afzal; Sana Ashraf; Khadeeja Rehman; Azhar Hussain; Zahir Ahmad Zahir (Environmental Monitoring and Assessment, 2018)

Influence of salinity and Fusarium oxysporum as the stress factors on morpho-physiological and yield attributes in onion - Amna Shoaib; Sidra Meraj; Nafisa; Kashif Ali Khan; Muhammad Azhar Javaid (Physiology and Molecular Biology of Plants, 2018)

Sustainable survival under climatic extremes: linking flood risk mitigation and coping with flood damages in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Muhammad Usman; M. Amjed Iqbal; Muhammad Arshad; M. Adnan Shahid; Klaus Müller (Environmental Science and Pollution Research, 2018)

Anaerococcus jeddahensis sp. nov., a New Bacterial Species Isolated From Healthy Nomadic Bedouin Woman From Saudi Arabia - Niokhor Dione; Sara Bellali; Muhammad Yasir; Esam I. Azhar; Fehmida Bibi; Mamadou Beye; Nicholas Armstrong; Frédéric Cadoret; Asif A. Jiman-Fatani; Nayel Helmy; Jaishriram Rathored; Noémie Labas; et al. (Current Microbiology, 2018)

Effects of intensive rice production practices on avian biodiversity in Southeast Asian managed wetlands - Nur Amira; Tengku Rinalfi; Badrul Azhar (Wetlands Ecology and Management, 2018)

Diagnosis and ecotoxicological risk assessment of 49 elements in sludge from wastewater treatment plants of Chongqing and Xiamen cities, China - Fidèle Suanon; Qiaoqiao Chi; Xiaoyong Yang; Hongjie Wang; Azhar Rashid; Bahareh Asefi; Daouda Mama; Chang-Ping Yu; Qian Sun (Environmental Science and Pollution Research, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Silicon-mediated growth and yield improvement of sunflower (Helianthus annus L.) subjected to brackish water stress - Syed Azhar Hussain; Muhammad Ansar Farooq; Javaid Akhtar; Zulfiqar Ahmad Saqib (Acta Physiologiae Plantarum, 2018)

Changes in the nutritional composition of maize flour due to Tribolium castaneum infestation and application of carbon dioxide to manage this pest - Khalid Mehmood; Mureed Husain; Muhammad Aslam; Muhammad Shoaib Ahmedani; Azhar Mehmood Aulakh; Farid Asif Shaheen (Environmental Science and Pollution Research, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Resveratrol analogue, (E)-N-(2-(4-methoxystyryl) phenyl) furan-2-carboxamide induces G2/M cell cycle arrest through the activation of p53–p21CIP1/WAF1 in human colorectal HCT116 cells - Foo Kit Cheah; Kok Hoong Leong; Noel Francis Thomas; Hui Kee Chin; Azhar Ariffin; Khalijah Awang (Apoptosis, 2018)

Biodiesel production from algae grown on food industry wastewater - Khadija Mureed; Shamsa Kanwal; Azhar Hussain; Shamaila Noureen; Sabir Hussain; Shakeel Ahmad; Maqshoof Ahmad; Rashid Waqas (Environmental Monitoring and Assessment, 2018)

Genetic characterization and diversity of circulating influenza A/H1N1pdm09 viruses isolated in Jeddah, Saudi Arabia between 2014 and 2015 - Anwar M. Hashem; Esam I. Azhar; Sarah Shalhoub; Turki S. Abujamel; Norah A. Othman; Abdulwahab B. Al Zahrani; Hanan M. Abdullah; Maha M. Al-Alawi; Anees A. Sindi (Archives of Virology, 2018)

Cancer Screening Perception Scale: Development and Construct Validation - Mohd Ihsani Mahmood; Shamsul Azhar Shah; Norfazilah Ahmad; Norazman Mohd Rosli (Journal of Cancer Education, 2018)

Consequence of HIV and HCV co-infection on host immune response, persistence and current treatment options - Sayed Sartaj Sohrab; Mohd Suhail; Ashraf Ali; Ishtiaq Qadri; Steve Harakeh; Esam I. Azhar (VirusDisease, 2018)

Ag@MnxOy: an effective catalyst for photo-degradation of rhodamine B dye - Muhammad Saeed; Aziz Ahmad; Rajender Boddula; Inamuddin; Atta ul Haq; Aisha Azhar (Environmental Chemistry Letters, 2018)

A machine learning framework involving EEG-based functional connectivity to diagnose major depressive disorder (MDD) - Wajid Mumtaz; Syed Saad Azhar Ali; Mohd Azhar Mohd Yasin; Aamir Saeed Malik (Medical & Biological Engineering & Computing, 2018)

In vitro growth inhibition and cytotoxicity of Euphorbia caducifolia against four human cancer cell lines and its phytochemical characterisation - Shaista Bano; Bina Shaheen Siddiqui; Ahsana Dar Farooq; Sabira Begum; Faheema Siddiqui; Muhammad Kashif; Mudassar Azhar (Natural Product Research, 2017)

Genetic analysis of a red tilapia (Oreochromis spp.) population undergoing three generations of selection for increased body weight at harvest - Azhar Hamzah; Ngo Phu Thoa; Nguyen Hong Nguyen (Journal of Applied Genetics, 2017)

Sensitivity of AGCM ‐simulated regional JJAS precipitation to different convective parameterization schemes - Muhammad Azhar Ehsan; Mansour Almazroui; Ahmed Yousef; O'Brien Enda; Michael K. Tippett; Fred Kucharski; Abdulrahman A. Alkhalaf (International Journal of Climatology, 2017)
This study examines the effects of convective parameterization schemes ( CPSs ) on the simulated June–September ( JJAS ) precipitation climatology, variability and predictability over southwestern Arabian Peninsula and northeast Africa during 1981–2014 within an atmospheric global climate model framework. The three CPSs used are: the simplified Arakawa–Schubert ( SAS ) scheme; the SAS scheme with Tokioka modification ( STOK ) and the Emanuel ( EMAN ) scheme coupled with a probability distribution function‐based cloud parameterization scheme. SAS and STOK overestimate JJAS total precipitation over the selected domain compared to observations, while EMAN underestimates. EMAN provides the most realistic distribution of precipitation and spatial distribution of convective precipitation despite the tendency for underestimating the total precipitation. The principal patterns of precipitation variability (as measured by the leading empirical orthogonal functions) in EMAN and STOK are clearly related to the observed pattern, while the maximum variability in SAS occurs in a completely different location. The El Niño Southern Oscillation‐related JJAS precipitation teleconnection simulated by the SAS scheme is very weak as compared to observations and other two CPSs . The signal‐to‐noise ratio estimated by SAS and STOK is very low as compared to EMAN . Correlation analysis shows that EMAN performs better than the other two CPSs . Low (high) outgoing longwave radiation ( OLR ) values are indicative of enhanced (suppressed) convection and hence more (less) cloud coverage. The root mean square error estimated for OLR in EMAN is lower than that of the other two CPSs . The vertical structure of specific humidity and temperature shows less error in EMAN than that of the other two CPSs , which could be a reason for better predictability over the region of interest.

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

The physical, mechanical and durability properties of sorghum bagasse particleboard by layering surface treatment - Apri Heri Iswanto; Wulandhari Aritonang; Irawati Azhar; Supriyanto; Widya Fatriasari (Journal of the Indian Academy of Wood Science, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

The role of glutamine synthetase in energy production and glutamine metabolism during oxidative stress - Nohaiah Aldarini; Azhar A. Alhasawi; Sean C. Thomas; Vasu D. Appanna (Antonie van Leeuwenhoek, 2017)

How hard they hit? Perception, adaptation and public health implications of heat waves in urban and peri-urban Pakistan - Sara Rauf; Khuda Bakhsh; Azhar Abbas; Sarfraz Hassan; Asghar Ali; Harald Kächele (Environmental Science and Pollution Research, 2017)

Climate variability and yield risk in South Asia’s rice–wheat systems: emerging evidence from Pakistan - Muhammad Arshad; T. S. Amjath-Babu; Timothy J. Krupnik; Sreejith Aravindakshan; Azhar Abbas; Harald Kächele; Klaus Müller (Paddy and Water Environment, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

An improvement in mass flux convective parameterizations and its impact on seasonal simulations using a coupled model - Ahmed Elsayed Yousef; M. Azhar Ehsan; Mansour Almazroui; Mazen E. Assiri; Abdulrahman K. Al-Khalaf (Theoretical and Applied Climatology, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Risk assessment for arsenic-contaminated groundwater along River Indus in Pakistan - Unaib Rabbani; Gohar Mahar; Azhar Siddique; Zafar Fatmi (Environmental Geochemistry and Health, 2017)

Validation of surgical site infection registration in colorectal surgery - Andreas Jonsson; Najia Azhar; Claes Hjalmarsson (Infectious Diseases, 2017)

Applications of polysaccharides (β-glucan) for physiological and biochemical parameters for evaluation rice tolerance under salinity stress at seedling stage - Arshad Naji Alhasnawi; Che Radziah Che Mohd Zain; Ahsan A. Kadhimi; Anizan Isahakb; Azhar Mohamad; Mehdi Farshad Ashraf; Wan Mohtar Wan Yusoff (Journal of Crop Science and Biotechnology, 2016)

Putative Roles for Metallothionein and HSP70 Genes in Relation with Heavy Metal Accumulation and Parasitic Cymothoid in the Fish Nemipterus furcosus - Do Dinh Thinh; Mohamad Hafiz Farhan Abdul Rasid; Zulaikha Mat Deris; Noor Azhar Mohamed Shazili; Gudrun De Boeck; Li Lian Wong (Archives of Environmental Contamination and Toxicology, 2016)

Depauperate Avifauna in Tropical Peat Swamp Forests Following Logging and Conversion to Oil Palm Agriculture: Evidence from Mist-netting Data - Ainil Hawa; Badrul Azhar; Marina Mohd Top; Akbar Zubaid (Wetlands, 2016)

Effects of fusaric acid treatment on the protocorm-like bodies of Dendrobium sonia-28 - Raheleh Dehgahi; Latiffah Zakaria; Azhar Mohamad; Alireza Joniyas; Sreeramanan Subramaniam (Protoplasma, 2016)

Synthesis, characterization, drug-likeness properties and determination of the in vitro antioxidant and cytotoxic activities of new 1,3,4-oxadiazole derivatives - Nafal Nazarbahjat; Azhar Ariffin; Zanariah Abdullah; Mahmood Ameen Abdulla; John Kwong Siew Shia; Kok Hoong Leong (Medicinal Chemistry Research, 2016)

RCD1 homologues and their constituent WWE domain in plants: analysis of conservation through phylogeny methods - Beena Siddiqua; Syeda Qamarunnisa; Abid Azhar (Biologia, 2016)

Accumulation of Trace Metals in Anadara granosa and Anadara inaequivalvis from Pattani Bay and the Setiu Wetlands - Siriporn Pradit; Noor Azhar Mohamed Shazili; Prawit Towatana; Wuttipong Saengmanee (Bulletin of Environmental Contamination and Toxicology, 2016)

The role of formate in combatting oxidative stress - Sean C. Thomas; Azhar Alhasawi; Christopher Auger; Abdelwahab Omri; Vasu D. Appanna (Antonie van Leeuwenhoek, 2016)

Effects of in situ habitat quality and landscape characteristics in the oil palm agricultural matrix on tropical understory birds, fruit bats and butterflies - Badrul Azhar; Chong Leong Puan; Najjib Aziz; Muhammad Sainuddin; Nurfatin Adila; Sohaimi Samsuddin; Siti Asmah; Muhamad Syafiq; Syafiq A. Razak; Ahmad Hafizuddin; Ainil Hawa; Syari Jamian (Biodiversity and Conservation, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Geochemical assessment of metal pollution and ecotoxicology in sediment cores along Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Nisar Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2015)

Bnsro1: A new homologue of Arabidopsis thaliana rcd1 from Brassica napus - Sadia Anjum; Saboohi Raza; Abid Azhar; Syeda Qamarunnisa (Biologia, 2015)

A comparison of molluscan communities in a section of the Nile River at Assiut, Egypt, with different chemical and thermal pollution - Khaleid F. Abd El-Wakeil; Ahmed H. Obuid-Allah; Azhar H. Mohamed; Fatma El-Zahraa A. Abd El-Aziz (Molluscan Research, 2015)

Non-structural flood risk mitigation under developing country conditions: an analysis on the determinants of willingness to pay for flood insurance in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Klaus Müller (Natural Hazards, 2015)

Thermal inactivation of Alkhumra hemorrhagic fever virus - Tariq A. Madani; El-Tayb M. E. Abuelzein; Esam I. Azhar; Hussein M. S. Al-Bar (Archives of Virology, 2014)

Resistance of the house fly Musca domestica (Diptera: Muscidae) to lambda-cyhalothrin: mode of inheritance, realized heritability, and cross-resistance to other insecticides - Naeem Abbas; Hafiz Azhar Ali Khan; Sarfraz Ali Shad (Ecotoxicology, 2014)

A new trypsin inhibitory phthalic acid ester from Heliotropium strigosum - Syed Majid Shah; Azhar-ul-Haq Ali Shah; Farhat Ullah; Sajid Hussain; Sher Bahadar Khan; Abdullah M. Asiri; Shabir Ahmad; Hidayatullah Khan; Umar Farooq (Medicinal Chemistry Research, 2014)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Ecological impacts of oil palm agriculture on forest mammals in plantation estates and smallholdings - Badrul Azhar; David B. Lindenmayer; Jeff Wood; Joern Fischer; Mohamed Zakaria (Biodiversity and Conservation, 2014)

Factors affecting sap transmission of Tomato leaf curl New Delhi begomovirus infecting sponge gourd in India - Sayed Sartaj Sohrab; Sajjad Karim; Anupam Varma; Esam I. Azhar; Bikash Mandal; Adel M. Abuzenadah; Adeel G. Chaudhary (Phytoparasitica, 2013)

A quantitative assessment of changes in seasonal potential predictability for the twentieth century - M. Azhar Ehsan; In-Sik Kang; Mansour Almazroui; M. Adnan Abid; Fred Kucharski (Climate Dynamics, 2013)

Assessing the response of indigenous loquat cultivar Mardan to phytohormones for in vitro shoot proliferation and rooting - Nadeem Akhtar Abbasi; Tariq Pervaiz; Ishfaq Ahmed Hafiz; Mehwish Yaseen; Azhar Hussain (Journal of Zhejiang University-SCIENCE B, 2013)

Interannual variability of rainfall over the Arabian Peninsula using the IPCC AR4 Global Climate Models - Mansour Almazroui; M. Adnan Abid; H. Athar; M. Nazrul Islam; M. Azhar Ehsan (International Journal of Climatology, 2013)
The interannual rainfall variability derived from the 22 Global Climate Model ( GCM ) simulations of the Intergovernmental Panel on Climate Change ( IPCC ) Fourth Assessment Report ( AR4 ) for the duration 1979–2000 is analysed and compared with the gridded observed dataset over the Arabian Peninsula. The annual cycle of the rainfall derived from these models is validated for the entire Arabian Peninsula, and separately for its two sub‐regions, named northern and southern Arabian Peninsula. The spatial patterns of the rainfall and the mean sea level pressure are analysed to judge the ability of the models to simulate the mean climatology of the Peninsula. This analysis reveals that out of the 22 IPCC AR4 GCM multi‐model datasets, only one group (composed of 5 models) is relatively better than all the others in simulating the interannual variability of the wet season rainfall for the northern sub‐region, and another group (also composed of 5 models) is likewise for the dry season rainfall climatology of the southern sub‐region, compared with the gridded dataset. The above two groups of models tend to fall within one‐sigma standard deviation of the mean seasonal rainfall derived from the gridded dataset. Moreover, only one model [ CCCMA‐CGCM3 ( T47 ) from Canada] is found to be relatively better in simulating the rainfall climatology for both the wet and the dry seasons (i.e. for the northern and the southern sub‐regions) simultaneously, compared with the observed data.

Total cell pooling in vitro: an effective isolation method for bone marrow-derived multipotent stromal cells - Ai-Sze Wee; Chin-Keong Lim; Azhar Mahmood Merican; Tunku Sara Ahmad; Tunku Kamarul (In Vitro Cellular & Developmental Biology - Animal, 2013)

Efficient DDT and trichlorophenol detoxification using NaBH4 and Devarda alloy - Abdul Ghaffar; Masaaki Tabata; Azhar Mashiatullah; Abdulaziz S. Alaamer (Environmental Chemistry Letters, 2013)

Resistance to conventional insecticides in Pakistani populations of Musca domestica L. (Diptera: Muscidae): a potential ectoparasite of dairy animals - Hafiz Azhar Ali Khan; Waseem Akram; Sarfraz Ali Shad (Ecotoxicology, 2013)

Effect of mid‐latitude blocking anticyclones on the weather of the Arabian Peninsula - H. Athar; Mansour Almazroui; M. Nazrul Islam; M. Adnan Abid; M. Azhar Ehsan (International Journal of Climatology, 2013)
The statistical relationships among the various 10°–70°E mid‐latitude blocking anticyclone parameters and the weather of the Arabian Peninsula (AP) (35°–60°E, 12°–32°N) over a 40‐year period (1968‐2007), on seasonal, interannual, decadal and long‐term scales, are studied. The studied parameters include the number of blocking anticyclone events, the duration, the intensity, and the longitude at the blocking anticyclone onset. It is found that 31% of the Northern Hemisphere mid‐latitude blocking anticyclone events occurred over the 10°–70°E longitudes, and out of these, the maximum number of mid‐latitude blocking anticyclone event onsets are at 30°E (24%). On the seasonal basis, the annual and decadal relationships of the 10°–70° blocking anticyclones with the El‐Niño Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO) indices are presented. The results show that the number of days the blocking anticyclones persists is sensitive to the ENSO phase. The mid‐latitude blocking anticyclone occurrence over the 10°–70°E longitudes is indicative of the reduced surface temperature variance, both upstream and downstream, during the blocking anticyclone period, over the AP. A shift in the mean surface temperature distribution occurs, in all seasons, during the blocking anticyclone period. The blocking anticyclones initiate a surface temperature change (both positive and negative) that persists even after the blocking anticyclone's decay. The AP surface weather during the months of October, November, and December is affected more by the occurrence of mid‐latitude blocking anticyclones over the 10°–70°E longitudes in the presence the of El‐Niño phase. Copyright © 2012 Royal Meteorological Society

Metal pollution and ecological risk assessment in marine sediments of Karachi Coast, Pakistan - Azhar Mashiatullah; Muhammad Zaman Chaudhary; Nasir Ahmad; Tariq Javed; Abdul Ghaffar (Environmental Monitoring and Assessment, 2013)

Trypsin-dependent hemagglutination of erythrocytes of a variety of mammalian and avian species by Alkhumra hemorrhagic fever virus - Tariq A. Madani; El-Tayeb M. E. Abuelzein; Huda Abu-Araki; Esam I. Azhar; Hussein M. S. Al-Bar (Archives of Virology, 2013)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Dracorhodin perchlorate inhibits PI3K/Akt and NF-κB activation, up-regulates the expression of p53, and enhances apoptosis - Azhar Rasul; Chuan Ding; Xiaomeng Li; Muhammad Khan; Fei Yi; Muhammad Ali; Tonghui Ma (Apoptosis, 2012)

Determination of radioactive elements and heavy metals in sediments and soil from domestic water sources in northern peninsular Malaysia - Bashir G. Muhammad; Mohammad Suhaimi Jaafar; Azhar Abdul Rahman; Farouk Abdulrasheed Ingawa (Environmental Monitoring and Assessment, 2012)

Regeneration in sugarcane via somatic embryogenesis and genomic instability in regenerated plants - Saboohi Raza; Syeda Qamarunisa; Mushtaq Hussain; Ishrat Jamil; Sadia Anjum; Abid Azhar; Javed Ahmed Qureshi (Journal of Crop Science and Biotechnology, 2012)

High dechlorination of PCBs catalysed by carbon under mild conditions - Abdul Ghaffar; Masaaki Tabata; Farhana Mazher; Azhar Mashiatullah (Environmental Chemistry Letters, 2012)

Superiority of the buffy coat over serum or plasma for the detection of Alkhumra virus RNA using real time RT-PCR - Tariq A. Madani; El-Tayeb M. E. Abuelzein; Esam I. Azhar; Moujahed Kao; Hussein M. S. Al-Bar; Huda Abu-Araki; Thomas G. Ksiazek (Archives of Virology, 2012)

Engineering broad-spectrum resistance against RNA viruses in potato - M. Arif; U. Azhar; M. Arshad; Y. Zafar; S. Mansoor; S. Asad (Transgenic Research, 2012)

Antitussive and toxicological evaluation of Vitex negundo - Rizwan-ul Haq; Azhar-ul-Haq Ali Shah; Arif-ullah Khan; Zahoor Ullah; Habib-ullah Khan; Rafeeq Alam Khan; Abdul Malik (Natural Product Research, 2012)

Implementation of herd health program to improve survival of Boer goats in Malaysia - Mohd Shahrom Salisi; Mohd Zamri Saad; Azhar Kasim (Tropical Animal Health and Production, 2012)

Altered tissue behavior of a non-aneurysmal descending thoracic aorta in the mouse model of Marfan syndrome - Darren Haskett; Jefferson J. Doyle; Connie Gard; Hwudaurw Chen; Corbie Ball; Mark A. Estabrook; Alejandra C. Encinas; Harry C. Dietz; Urs Utzinger; Jonathan P. Vande Geest; Mohamad Azhar (Cell and Tissue Research, 2012)

Transforming growth factor beta signaling in adult cardiovascular diseases and repair - Thomas Doetschman; Joey V. Barnett; Raymond B. Runyan; Todd D. Camenisch; Ronald L. Heimark; Henk L. Granzier; Simon J. Conway; Mohamad Azhar (Cell and Tissue Research, 2012)

Characterisation of Plasmodium falciparum aspartic protease inhibition by piperidine derivatives - Zafar Saied Saify; Mehrun Nisa; Kaniz Fizza Azhar; M. Kamran Azim; Huma Rasheed; Nousheen Mushtaq; M. Arshad Arain; Shazia Haider; Manawar Khanum; Waseem Ahmed (Natural Product Research, 2011)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Continuous Production of Dextran from Immobilized Cells of Leuconostoc mesenteroides KIBGE HA1 Using Acrylamide as a Support - Shah Ali Ul Qader; Afsheen Aman; Abid Azhar (Indian Journal of Microbiology, 2011)

Scale-dependent selection of greenness by African elephants in the Kruger-private reserve transboundary region, South Africa - Jason P. Marshal; Azhar Rajah; Francesca Parrini; Michelle Henley; Stephen R. Henley; Barend F. N. Erasmus (European Journal of Wildlife Research, 2011)

Accumulation of glucosinolates and nutrients in pakchoi (Brassica campestris L. ssp. chinensis var. communis) two cultivar plants exposed to sulfur deficiency - Keling Hu; Zhujun Zhu; Yunxiang Zang; Syed Azhar Hussain (Horticulture, Environment, and Biotechnology, 2011)

Characterization of resistance gene analogs from Gossypium arboreum and their evolutionary relationships with homologs from tetraploid cottons - Muhammad Tehseen Azhar; Imran Amin; Aftab Bashir; Shahid Mansoor (Euphytica, 2011)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)

Genetic improvement of Nile tilapia ( Oreochromis niloticus ) with special reference to the work conducted by the WorldFish Center with the GIFT strain - Raul W. Ponzoni; Nguyen Hong Nguyen; Hooi Ling Khaw; Azhar Hamzah; Khairul Rizal Abu Bakar; Hoong Yip Yee (Reviews in Aquaculture, 2011)
We mainly (but not exclusively) draw on research and development work carried out by The WorldFish Center (WorldFish). We review in detail the current state of development of a selection program that has had a main focus on growth rate and body traits. We also present some new, unpublished, information. There is evidence of sustained gains of 10–15% per generation over more than six generations. To date, these gains have not been accompanied by any undesirable correlated response. However, the prospects of altering sexual dimorphism and the shape of the fish appear to be very limited. We also examine the issue of an appropriate environment for selection. Not surprisingly, experimental evidence on genotype by environment interactions suggests that this is more likely to be of importance when the environments in question are markedly dissimilar. We argue that no universal guidelines can be prescribed with regard to the need for more than one selection program to cope with different production environments, but rather, each case should be examined in its own right. Finally, we discuss traits likely to be candidates for inclusion in future, more elaborate, breeding objectives for Nile tilapia ( Oreochromis niloticus ), comment on selection methods that may be implemented in the future and conclude by stressing the need to maintain an effective population size in selection lines to ensure their sustainability over time.

Both malvaceous and non-malvaceous betasatellites are associated with two wild cotton species grown under field conditions in Pakistan - Muhammad Tehseen Azhar; Imran Amin; Zahid Iqbal Anjum; Muhammad Arshad; Rob W. Briddon; Shahid Mansoor (Virus Genes, 2010)

Analysis of heavy metal concentrations in sediments of selected estuaries of Malaysia—a statistical assessment - Abbas F. M. Alkarkhi; Norli Ismail; Aness Ahmed; Azhar mat Easa (Environmental Monitoring and Assessment, 2009)

Synthesis and evaluation of lanthanide ion DOTA–tetraamide complexes bearing peripheral hydroxyl groups - Azhar Pasha; Mai Lin; Gyula Tircsó; Cynthia L. Rostollan; Mark Woods; Garry E. Kiefer; A. Dean Sherry; Xiankai Sun (JBIC Journal of Biological Inorganic Chemistry, 2009)

Detection of the patulin-producing potential of some Paecilomyces variotii strains isolated from the air samples of Jeddah City, Saudi Arabia, using the RAPD-PCR technique - Fardos Bokhari; Youssuf Gherbawy; Azhar Najjar (Aerobiologia, 2009)

Genetic basis of variation for lint color, yield, and quality in cotton ( Gossypium hirsutum L.) - A. A. Khan; F. M. Azhar; I. A. Khan; A. H. Riaz; M. Athar (Plant Biosystems, 2009)

Multivariate analysis of heavy metals concentrations in river estuary - Abbas F. M. Alkarkhi; Anees Ahmad; Norli Ismail; Azhar Mat Easa (Environmental Monitoring and Assessment, 2008)

Increased GABAB Receptor Subtype Expression in the Nucleus of the Solitary Tract of the Spontaneously Hypertensive Rat - Emma J. Spary; Azhar Maqbool; Sikha Saha; Trevor F. C. Batten (Journal of Molecular Neuroscience, 2008)

Fluoride Concentration in Drinking Water of Karachi City (Pakistan) - Azhar Siddique; Majid Mumtaz; Sumayya Saied; Zahida Karim; Nayyer A. Zaigham (Environmental Monitoring and Assessment, 2006)

Peroxisome proliferator-activated receptor-α selective ligand reduces adiposity, improves insulin sensitivity and inhibits atherosclerosis in LDL receptor-deficient mice - Rai Ajit K. Srivastava; Ravi Jahagirdar; Salman Azhar; Somesh Sharma; Charles L. Bisgaier (Molecular and Cellular Biochemistry, 2006)

Xanthine oxidase inhibiting flavonol glycoside from Amberboa ramosa - Sher Bahadar Khan; Nighat Afza; Abdul Malik; Azhar-Ul-Haq; Shagufta Perveen; Ijaz Ahmad; Asma Ejaz; M. Iqbal Choudhary (Natural Product Research, 2006)

Genetic basis of inosine triphosphate pyrophosphohydrolase deficiency - Satoshi Sumi; Anthony Marinaki; Monica Arenas; Lynette Fairbanks; Monsor Shobowale-Bakre; David Rees; Swee Thein; Azhar Ansari; Jeremy Sanderson; Ronney De Abreu; Anne Simmonds; John Duley (Human Genetics, 2002)

Delayed Changes in Regional Brain Energy Metabolism following Cerebral Concussion in Rats - Marek Buczek; Jamie Alvarez; Jaffar Azhar; Yinong Zhou; W. David Lust; Warren R. Selman; Robert A. Ratcheson (Metabolic Brain Disease, 2002)

The Influence of Conceptual Flow Simulation Model Parameters on Model Solution - Aqeel Azhar Khan; S. M. Saeed Shah; H. F. Gabriel (Water Resources Management, 2002)

Non-redundant tumour suppressor functions of transforming growth factor beta in breast cancer - Mohamad Azhar (Journal of Biosciences, 2001)

Purification and the effect of manganese ions on the activity of carboxymethylcellulases fromAspergillus niger andCellulomonas biazotea - K. S. Siddiqui; M. J. Azhar; M. H. Rashid; T. M. Ghuri; M. I. Rajoka (Folia Microbiologica, 1997)

Stability and identification of active-site residues of carboxymethylcellulases fromAspergillus niger andCellulomonas biazotea - K. S. Siddiqui; M. J. Azhar; M. H. Rashid; M. I. Rajoka (Folia Microbiologica, 1997)

Ultrastructural alterations produced in cockerels after mercuric chloride toxicity and subsequent interaction with an organophosphate insecticide - Muhammad Azhar Chishti; Tadeusz Rotkiewicz (Archives of Environmental Contamination and Toxicology, 1992)